Defoaming agent composition, water-based coating composition, and article

By using a defoaming agent composition with a specific structure of nonionic surfactants, polymers and organic solid particles, the problem of defoaming deactivation of existing defoaming agents during high shear and long-term dispersion processes is solved. It achieves excellent shear resistance and defoaming effects, while avoiding the shrinkage of the coating film and hindering topcoatability.

CN119325499APending Publication Date: 2025-01-17KUSUMOTO CHEM
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380044922.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-07-10
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing defoaming agents are defoaming in the process of high shearing and long-term dispersion, and silicone defoaming agents have problems of shrinking and hindering surface coating properties. Compound defoaming agents may damage the smoothness of the coating film. and shine.

Method used

Adopt a defoaming agent composition containing a hydrophilic part with a specific structure, a nonionic surfactant with an appropriate HLB range, a polymer with a specific SP value and weight average molecular weight, and organic solid particles to ensure that it can survive high shear and long periods of time. Maintains excellent shear resistance and defoaming effects under dispersion conditions.

Benefits of technology

It achieves excellent shear resistance and defoaming effects under high shear and long-term dispersion conditions, avoids the shrinkage of the coating film and hinders topcoatability, while maintaining the smoothness and gloss of the coating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169376740000301
    Figure BDA0005169376740000301
  • Figure BDA0005169376740000351
    Figure BDA0005169376740000351
  • Figure BDA0005169376740000411
    Figure BDA0005169376740000411
Patent Text Reader

Abstract

Provided are: a defoaming agent composition which is capable of forming a coating film having an excellent coating appearance, has excellent shear resistance, and does not impair topcoat properties; a water-based coating composition containing the defoaming agent composition; and an article covered with a coating agent containing the defoaming agent composition. A defoaming agent composition for a water-based coating material contains: a nonionic surfactant (A) having, in the molecule, at least one hydrophilic moiety selected from the group consisting of an ethylene glycol moiety, a polyethylene glycol moiety, and a polyol moiety, and having an HLB of 1-16; a polymer (B) that does not have the hydrophilic part in the molecule, has an SP value of 7.5-12, and has a weight-average molecular weight of 400-1000000; and organic solid microparticles (C) which are in a solid state at 25 DEG C in the defoaming agent composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a defoamer composition, a water-based coating composition and an article. Background Art

[0002] In recent years, the trend of attaching importance to the appearance of coatings in the field of water-based coatings has been increasing year by year. If bubbles remain in the coating film during coating, the coating appearance will be significantly damaged. Therefore, the performance required of defoamers added to coatings has also increased in recent years with the trend of attaching importance to the appearance of coatings.

[0003] Here, as a defoaming agent that can also be used for applications requiring a high appearance, for example, a defoaming agent described in Patent Document 1 is proposed. In addition, as defoaming agents with excellent defoaming effects, silicone defoaming agents (for example, see Patent Document 2) and composite defoaming agents (for example, see Patent Document 3) can be cited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 4526584

[0007] Patent Document 2: Japanese Patent Application Publication No. 2001-212403

[0008] Patent Document 3: Japanese Patent Publication No. 01-6803 Summary of the invention

[0009] Technical Problems to be Solved by the Invention

[0010] Generally, silicone defoamers have excellent defoaming properties due to their extremely low surface tension. On the other hand, the silicone component bleeds into the coating surface, causing shrinkage (cissing, crawling; Japanese: ハジキ) or hindering the surface coating. These adverse effects cannot be confirmed in a short period of time in laboratory-scale tests or actual coating processes. In mass production, a single problem may cause great losses. Therefore, in coatings for applications that emphasize high appearance, multi-layer coating systems, production line coating, etc., the formulation of silicone materials is avoided in most cases. As for defoamers, the use of silicone defoamers is also avoided. On the other hand, composite defoamers contain microparticles with a hydrophobic surface and have high defoaming properties caused by the hydrophobic surface. Therefore, they are often used in the expectation of excellent defoaming effects.

[0011] However, due to the recent improvement in functionality of water-based paints, raw materials that are difficult to disperse in water are often used. If these raw materials are not fully micronized or dispersed, the coating appearance is affected. Therefore, in recent years, the dispersion process is prolonged, or the shear force applied to the paint is increased (high shearing) during the dispersion process.

[0012] However, the composite defoamer described in Patent Document 3 and the defoamer described in Patent Document 1 may lose their defoaming properties in the process of long-term dispersion or high-shear dispersion. Therefore, a defoamer having resistance to defoaming properties due to the application of shear force to the coating (hereinafter referred to as "shear resistance") is required. In addition, there are cases where the coating is recycled to prevent the sedimentation and separation of components in the coating, and in this case, long-term shear resistance is required.

[0013] Furthermore, in the composite defoamer, the presence of fine particles may impair the smoothness and gloss of the coating film.

[0014] Therefore, the present invention has been made in view of the above circumstances, and an object of the present invention is to provide a defoamer composition that can form a coating film having an excellent coating appearance and having excellent shear resistance and does not hinder topcoatability, a water-based coating composition containing the defoamer composition, and an article covered with a coating agent containing the defoamer composition.

[0015] Technical solutions for solving technical problems

[0016] In order to solve the above-mentioned technical problems, the present inventors have conducted repeated and earnest studies, and as a result, have found that it is possible to provide a defoamer composition for water-based paints that can form a coating film with excellent coating appearance and has excellent shear resistance and does not hinder topcoatability by adding a nonionic surfactant having a hydrophilic part with a specific structure and an HLB within a specific range, a polymer having an SP value and a weight average molecular weight within a specific range, and organic solid particles as components of the defoamer composition, and based on this finding, the present invention has been completed.

[0017] That is, the present invention is a defoamer composition, which is a defoamer composition for water-based coatings, characterized in that it contains: a nonionic surfactant (A) having at least one hydrophilic part selected from the group consisting of an ethylene glycol part, a polyethylene glycol part and a polyol part in the molecule, and an HLB of 1 to 16; a polymer (B) not having the hydrophilic part in the molecule, an SP value of 7.5 to 12, and a weight-average molecular weight of 400 to 1,000,000; and organic solid particles (C) that are in a solid state in the defoamer composition at 25°C.

[0018] In one embodiment of the present invention, the nonionic surfactant (A) may be one or more selected from the group consisting of ethylene glycol fatty ethers, polyoxyalkylene fatty ethers, polyoxyalkylene aromatic ethers, polyoxyalkylene fatty acid esters, oxyalkylene addition derivatives of castor oil, oxyalkylene addition derivatives of hydrogenated castor oil, polyoxyalkylene polyol ethers, polyol fatty acid esters, oxyalkylene addition derivatives of polyol fatty acid esters, polyoxyalkylene alkylamides, acetylene glycols and their derivatives, oxyalkylene addition derivatives of acetylene glycols, polyoxyethylene-polyoxypropylene block copolymers, and polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers.

[0019] In other embodiments of the present invention, the polymer (B) may be one or more polymers selected from the group consisting of polyvinyl alkyl ether, polybutadiene, polybutene, polyisoprene, poly-alpha-olefin, polyalkyl (meth) acrylate, copolymers of dibasic acid esters, polyvinyl fatty acid esters, copolymers of alkyl (meth) acrylate and vinyl fatty acid ester, and polyalkylene glycol derivatives (wherein the polyalkylene glycol derivative does not have the ethylene glycol portion, the polyethylene glycol portion and the polyol portion, and the weight average molecular weight of the polyalkylene glycol derivative is 400 to 1,000,000).

[0020] In another embodiment of the present invention, the organic solid fine particles (C) may be one or more solid fine particles selected from the group consisting of amide, urea, polyethylene, oxidized polyethylene, acid-modified polyethylene, and hydrogenated castor oil.

[0021] In this case, the amide is preferably a fatty acid diamide obtained by reacting a fatty acid selected from the group consisting of an alkyl fatty acid and a hydroxy fatty acid and containing at least one hydroxy fatty acid, with a diamine containing one or more diamines selected from the group consisting of an alkylenediamine having 2 to 6 carbon atoms and m-xylylenediamine.

[0022] In another aspect of the present invention, it is preferred that the aspect ratio of the crystals of the organic solid fine particles (C) is 1.1-100.

[0023] In another embodiment of the present invention, the defoamer composition may further contain an organic medium (D) which is liquid at 25° C. other than water having no hydrophilic part in the molecule, wherein the weight average molecular weight of the organic medium (D) is less than 400.

[0024] In this case, the organic medium (D) may be one or more selected from the group consisting of hydrocarbon oils, alcohols, glycol ethers, and glycol esters.

[0025] In another aspect of the present invention, it is preferred that the defoaming agent composition does not contain a silicone compound.

[0026] In addition, the present invention is a water-based coating composition, characterized by comprising: the above-mentioned defoamer composition; and a water-based resin.

[0027] Furthermore, the present invention is an article coated with a coating agent containing the above-mentioned defoaming agent composition.

[0028] Effects of the Invention

[0029] According to the present invention, a defoamer composition, an aqueous coating composition containing the defoamer composition, and an article covered with a coating agent containing the defoamer composition can be provided, wherein the defoamer composition contains a specific nonionic surfactant, a polymer, and organic solid particles as components, thereby forming a coating film having an excellent coating appearance and excellent shear resistance, and does not hinder topcoatability. DETAILED DESCRIPTION

[0030] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0031] [Defoaming agent composition]

[0032] The defoamer composition of the present invention is an additive for suppressing the generation of bubbles caused by the presence of multiple surfactants in water-based paints, and contains as essential components a nonionic surfactant (A) having a hydrophilic part with a specific structure and an HLB within a specific range, a polymer (B) having an SP value and a weight average molecular weight within a specific range, and organic solid particles (C). Thus, according to the present invention, a defoamer composition for water-based paints can be provided that can form a coating film with an excellent coating appearance, has excellent shear resistance, and does not hinder topcoatability.

[0033] Here, "defoaming property" in the present invention refers to the performance of making bubbles generated in water-based paint disappear. "Shear resistance" in the present invention refers to, as mentioned above, the resistance to deactivation of defoaming property with respect to the application of shear force to the coating, in other words, the performance of suppressing the defoaming property deactivation of the defoaming agent when shear force is applied to the coating. In addition, "top coating property" in the present invention refers to, in a coating system consisting of multiple layers, for a coated coating film (hereinafter, recorded as "primer coating film".), when further coating (hereinafter, recorded as "top coating".) coating is applied on its surface, it means that any one or both of the problems of coating without shrinkage, etc., and peeling, etc., are not generated between the top coating film and the primer coating film. In addition, the top coating property is usually to make a multilayer coating film and evaluate it by performing a test of the adhesion of the top coating film relative to the primer coating film, but it can also be simply evaluated by measuring the contact angle on the primer coating film surface. In the case of evaluating by contact angle, a liquid for contact angle evaluation can also be used in a topcoat or water-based coating, particularly, a cosolvent (organic solvent prepared in the coating), water containing a cosolvent, or water alone, and the lower the contact angle of the droplet of the liquid for contact angle evaluation dripped on the primer coating film within the range of less than 90°, the better the topcoatability is evaluated. Hereinafter, these essential components and the optional components contained in the defoamer composition of the present invention are described in detail.

[0034] (Nonionic surfactant (A))

[0035] The nonionic surfactant (A) of the present invention is a component for exerting defoaming property, and is a component added in order to improve the permeability of the defoamer to the bubble film. In addition, the nonionic surfactant (A) also has a function as a stabilizer for making the defoaming droplets containing organic solid particles (C) or the organic solid particles (C) themselves stably present in the water-based coating. In addition, the surfactant refers to an organic functional agent with the performance of reducing the surface tension of the liquid. For example, since hydrogenated castor oil (castor solidified oil) as a triglyceride of fatty acid is not a surfactant, it is not included in the nonionic surfactant (A).

[0036] As the nonionic surfactant (A) of the present invention, a nonionic surfactant having at least one hydrophilic portion selected from the group consisting of an ethylene glycol portion, a polyethylene glycol portion and a polyol portion in the molecule and having an HLB of 1 to 16 can be used.

[0037] The above-mentioned "hydrophilic part" is defined as one or more parts selected from the group consisting of ethylene glycol part, polyethylene glycol part, and polyol part existing in the molecule of nonionic surfactant (A). The ethylene glycol part refers to oxyethylene represented by -CH2CH2O-. The polyethylene glycol part refers to -(CH2CH2O) n -(n≥2). The polyol portion refers to, when the nonionic surfactant (A) is a derivative of a divalent or higher alcohol, a portion obtained by removing a monovalent substituent and an acyl group consisting of only hydrocarbons with a carbon number of 1 or more from a partial structure of a molecule derived from an organic group having two or more hydroxyl groups, and is not equivalent to an alkylene glycol or a polyalkylene glycol. In addition, when the "hydrophilic portion" is composed only of ethylene glycol or diethylene glycol, the hydrophobic portion (the portion other than the "hydrophilic portion" present in the molecule of the nonionic surfactant (A)) is limited to having a carbon number of 9 or more.

[0038] In addition, when the HLB of the nonionic surfactant (A) is less than 1, the compatibility with water is poor, and there is a possibility that the nonionic surfactant component itself separates in the water-based paint. On the other hand, when the HLB of the nonionic surfactant (A) is greater than 16, the affinity for water is too high, so other components of the defoamer cannot be fully stabilized, and there is a possibility that coagulation occurs and other defoaming components separate in the water-based paint.

[0039] As the mechanism of action of the defoamer, it is known that the defoamer droplets that lack affinity for aqueous media intrude into the interior of the bubble membrane, and the droplets penetrate the bubble membrane, thereby breaking the bubble starting from the droplets. Based on this, it can be considered that highly hydrophobic substances, that is, substances with low HLB values, have potential excellent bubble breaking properties. On the other hand, the defoamer droplets require a size that can penetrate into the bubble membrane. Therefore, a certain degree of hydrophilicity is required. The higher the hydrophilicity, the higher the dispersibility in water, so the droplets become smaller. On the contrary, in the case of low hydrophilicity, the droplets become larger. When the droplet diameter is too small, it cannot penetrate the bubble membrane, and when it is too large, it cannot invade the bubble membrane. In either case, the defoaming function is not exhibited. Therefore, in order to control the droplet diameter, there is an appropriate HLB range.

[0040] When the nonionic surfactant (A) is within an appropriate HLB range, it is more preferred because it has defoaming properties. From this viewpoint, the HLB of the nonionic surfactant (A) is preferably 2 to 16, and more preferably 3 to 16.

[0041] In addition, the nonionic surfactant (A) has the function of making the polymer (B), the organic solid particles (C), and the organic medium (D) which are other components in the defoamer composition of the present invention uniform in the defoamer composition. Furthermore, the nonionic surfactant (A) controls the droplets mixed with each component in the water-based paint to an appropriate particle size so that it can function as a defoamer, and contributes to the development of the defoaming function by stabilizing the dispersion.

[0042] The HLB in the present invention is calculated by the following formula according to the Griffin method.

[0043] HLB = 20 × total formula weight of hydrophilic part / molecular weight

[0044] The hydrophilic part of the above formula is defined as above.

[0045] <Specific example>

[0046] As the nonionic surfactant (A) of the present invention, a nonionic surfactant having the above-mentioned hydrophilic part and having an HLB value in the above-mentioned range can be selected, and a nonionic surfactant that is in a liquid state in the liquid medium contained in the composition at 25°C and does not exist in a solid state (that is, does not exist in the defoamer composition as fine particles) can be selected. As an example of a method for judging whether a compound having the above-mentioned hydrophilic part and having an HLB value in the above-mentioned range contained in the defoamer composition of the present invention corresponds to the nonionic surfactant (A) of the present invention, the following method can be cited. For example, for a mixed liquid of liquid medium components other than the compound to be judged contained in the defoamer composition, after dispersing the compound to be judged within a range of not more than 50% by mass, filtering the dispersion, and further washing with the above-mentioned mixed liquid, when no filtration residue is obtained, it can be judged that the compound to be judged is a nonionic surfactant (A). On the other hand, when a filtration residue is obtained after the above-mentioned filtration and washing, it can be judged that the compound to be judged is a nonionic surfactant (A) by confirming that the compound to be judged is not contained by qualitative analysis.

[0047] As the nonionic surfactant (A), for example, one or more of ethylene glycol fatty ethers, polyoxyalkylene fatty ethers, polyoxyalkylene aromatic ethers, polyoxyalkylene fatty acid esters, oxyalkylene addition derivatives of castor oil, oxyalkylene addition derivatives of hydrogenated castor oil, polyoxyalkylene polyol ethers, polyol fatty acid esters, oxyalkylene addition derivatives of polyol fatty acid esters, polyoxyalkylene alkylamides, acetylene glycols and derivatives thereof, oxyalkylene addition derivatives of acetylene glycols, polyoxyethylene-polyoxypropylene block copolymers, and polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers can be used.

[0048] As the ethylene glycol aliphatic ether, for example, an ethylene glycol aliphatic ether in which an aliphatic chain having 9 to 22 carbon atoms forms an ether bond with ethylene glycol can be used.

[0049] As the polyoxyalkylene fatty ether, for example, polyoxyethylene fatty ether, polyoxyethylene-polyoxypropylene fatty ether, etc., polyoxyalkylene fatty ether having 1 to 22 carbon atoms can be used. As the polyoxyalkylene aromatic ether, for example, polyoxyethylene aromatic ether, polyoxyethylene-polyoxypropylene aromatic ether, etc., polyoxyalkylene aromatic ether having 6 to 28 carbon atoms can be used. As the polyoxyalkylene fatty acid ester, for example, polyoxyethylene fatty acid ester, polyoxyethylene-polyoxypropylene fatty acid ester, etc., polyoxyalkylene fatty acid ester having 1 to 22 carbon atoms can be used.

[0050] As the oxyalkylene addition derivative of castor oil or hydrogenated castor oil, for example, polyoxyalkylene castor oil ethers such as polyoxyethylene castor oil ether and polyoxyethylene-polyoxypropylene castor oil ether, polyoxyalkylene castor oil ethers such as polyoxyethylene cured castor oil ether and polyoxyethylene-polyoxypropylene cured castor oil ether, polyoxyethylene castor oil ether fatty acid esters, polyoxyalkylene castor oil ether fatty acid esters such as polyoxyethylene-polyoxypropylene castor oil ether fatty acid esters, polyoxyethylene cured castor oil ether fatty acid esters (for example, polyoxyethylene cured castor oil monoisostearate, polyoxyethylene cured castor oil triisostearate, etc.), polyoxyalkylene cured castor oil ether fatty acid esters such as polyoxyethylene-polyoxypropylene cured castor oil ether fatty acid esters, and the like can be used.

[0051] Here, for example, when an oxyalkylene adduct of castor oil or hydrogenated castor oil is used, the number of moles of oxyalkylene (EO: ethylene oxide) added to castor oil or hydrogenated castor oil is preferably 5 to 100 mol, more preferably 5 to 60 mol. By setting the number of moles of EO added within the above range, the defoaming property and shear resistance of the defoamer of the present invention can be improved.

[0052] As the polyoxyalkylene polyol ether, for example, polyoxyalkylene polyol ethers obtained by adding oxyalkylene groups such as oxyethylene, oxypropylene, and oxybutylene to polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, monosaccharides, disaccharides, trisaccharides, oligosaccharides, polysaccharides, sorbitan, etc. having a glucose and fructose backbone can be used. As the polyol fatty acid ester, for example, esters of polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, monosaccharides, disaccharides, trisaccharides, oligosaccharides, polysaccharides, sorbitan, etc. having a glucose and fructose backbone and fatty acids such as acetic acid, propionic acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, oleic acid, 12-hydroxystearic acid, linoleic acid, linolenic acid, behenic acid, and erucic acid can be used. As the polyol fatty acid ester oxyalkylene addition derivative, for example, a polyol fatty acid ester oxyalkylene addition derivative obtained by adding oxyalkylene such as oxyethylene, oxypropylene, oxybutylene, etc. to the above-mentioned polyol fatty acid ester can be used. As the polyoxyalkylene alkylamide, for example, polyoxyethylene stearamide, polyoxyethylene oleamide, etc. can be used.

[0053] As acetylene glycol and its derivatives, and oxyalkylene addition derivatives of acetylene glycol, commercially available products can be used, for example, Surfynol (registered trademark: product name of Nissin Chemical Industry Co., Ltd.) series, Acetylenol (registered trademark: product name of Kawaken Fine Chemicals Co., Ltd.) series, etc. can be mentioned.

[0054] The number of moles of ethylene oxide (EO) added to the acetylene glycol or acetylene glycol derivative is preferably 1 to 10. From the viewpoint of improving the defoaming property of the defoaming agent of the present invention, the number of moles of EO added is more preferably 1 to 4.

[0055] As the polyoxyethylene-polyoxypropylene block copolymer or the polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer, for example, a block copolymer in which the total mass of the oxyethylene block in the copolymer molecule is 10% to 50% by mass (more preferably 10% to 20% by mass) and the weight average molecular weight of the oxypropylene block is 700 to 4000 (more preferably 3000 to 4000) can be used. Within the above range, a liquid type block copolymer is more preferred.

[0056] In the specific examples described above, polyoxyethylene-hydrided castor oil, triisostearate polyoxyethylene-hydrided castor oil, or the like is preferably used in order to improve defoaming properties.

[0057] <Content>

[0058] The content of the above nonionic surfactant (A) is preferably 5% by mass to 80% by mass when the total mass of all components in the defoaming agent composition is taken as 100% by mass. By making the content of the nonionic surfactant (A) 5% by mass to 80% by mass, sufficient defoaming properties can be exhibited. In order to further improve the defoaming effect, it is further preferred to make the content of the nonionic surfactant (A) 10% by mass to 50% by mass.

[0059] (Polymer (B))

[0060] The polymer (B) of the present invention is a component for exhibiting defoaming properties and is a component added to improve the penetration of the defoaming agent into the foam film. As the polymer (B), a polymer having an SP value of 7.5 to 12 and a weight average molecular weight of 400 to 1,000,000 is used. In addition, as the polymer (B), a polymer that does not have the above hydrophilic moiety (ethylene glycol moiety, polyethylene glycol moiety, polyol moiety) in the molecule and has a liquid or rubbery form, or a polymer that is solid at 25°C but is in a liquid state and does not exist in a solid state in the liquid medium contained in the composition at 25°C (that is, does not exist as fine particles in the defoaming agent composition) is selected. The liquid one can be used alone, and the rubbery and solid ones are dissolved and used with a liquid component.

[0061] <SP value / Weight average molecular weight>

[0062] The SP value of the polymer (B) of the present invention is in the range of 7.5 to 12. When the SP value is less than 7.5, there may be defects in the coating appearance such as shrinkage and seeding. On the other hand, when the SP value is greater than 12, the defoaming effect is lacking, and satisfactory defoaming properties may not be obtained. In addition, in order to further improve the defoaming properties, it is preferred that the SP value is 7.5 to 11, more preferably 8.0 to 9.5, and further preferably 8.0 to 9.0.

[0063] As the SP value in the present invention, the value calculated by Fedors' method is used, and the unit is (cal / cm 3 ) 1 / 2 . Fedors' method is a method for estimating the SP value based on the molecular structure, and the SP value can be estimated based on the relationship between the cohesive energy (cal / mol) and the molar molecular volume (cm3 / mol) of each atomic group.

[0064] In addition, the weight average molecular weight of the polymer (B) of the present invention is in the range of 400 to 1,000,000. When the weight average molecular weight is less than 400, sufficient defoaming property cannot be exerted. On the other hand, when the weight average molecular weight is greater than 1,000,000, it is difficult to evenly disperse the polymer (B) in the coating, resulting in problems such as shrinkage and cratering. In addition, in order to further improve the defoaming property, the preferred weight average molecular weight is 400 to 300,000.

[0065] The weight average molecular weight in the present invention is a value calculated based on the molecular weight of standard polystyrene from a chromatogram measured by gel permeation chromatography (GPC).

[0066] <Specific example>

[0067] The polymer (B) of the present invention is a polymer having the above-mentioned SP value and weight average molecular weight, and does not have the above-mentioned ethylene glycol part, the above-mentioned polyethylene glycol part, and the above-mentioned polyol part. Here, the "polymer (B)" in the present invention is a compound having a monomer unit as a repeating unit and a degree of polymerization of 3 or more, or a derivative thereof. As the polymer (B), for example, one or more polymers selected from polyvinylalkylether, polybutadiene, polybutene, polyisoprene, polyalphaolefin, polyalkyl (meth) acrylate, copolymers of dibasic acid esters, polyvinyl fatty acid esters, copolymers of alkyl (meth) acrylates and vinyl fatty acid esters, and polyalkylene glycol derivatives (wherein the polyalkylene glycol derivatives do not have the above-mentioned ethylene glycol part, the above-mentioned polyethylene glycol part, and the above-mentioned polyol part, and the weight average molecular weight of the above-mentioned polyalkylene glycol derivatives is 400 to 1,000,000.) can be preferably used.

[0068] The polyvinyl alkyl ether is obtained by polymerizing a vinyl ether monomer having an alkyl group having 1 to 18 carbon atoms. Examples of the vinyl ether monomer include vinyl methyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, hexyl vinyl ether, n-octyl vinyl ether, 2-ethylhexyl vinyl ether, isononyl vinyl ether, dodecyl vinyl ether, tetradecyl vinyl ether, hexadecyl vinyl ether, octadecyl vinyl ether, and the like. One or more of these monomers may be arbitrarily selected and used.

[0069] Polyvinyl alkyl ether is obtained by polymerizing the above monomers by cationic polymerization. The weight average molecular weight of polyvinyl alkyl ether is preferably 1000 to 500000, and more preferably 2000 to 300000. When the weight average molecular weight is less than 1000, it may not be able to exert sufficient defoaming performance. When the weight average molecular weight is greater than 500000, it is difficult to be evenly dispersed in the coating, and problems such as shrinkage and shrinkage cavities may occur.

[0070] As polybutadiene, homopolymers and copolymers of 1,3-butadiene (CH2=CH-CH=CH2) or 1,2-butadiene (CH2=C=CH-CH3) can be used. In addition, commercially available polybutadiene can also be used. As commercially available polybutadiene, there are homopolymers, hydrogenated types, terminal carboxylic acid type, terminal hydroxyl type, etc. As homopolymers, for example, there are B-1000 (15-25mers: number average molecular weight of about 1000), B-2000 (30-40mers: number average molecular weight of about 2000), B-3000 (45-65mers: number average molecular weight of about 3000) (all manufactured by Nippon Soda Co., Ltd.), etc. As hydrogenated types, for example, there are BI-2000 (30-40mers: number average molecular weight of about 2000), BI-3000 (45-65mers: number average molecular weight of about 3000) (both manufactured by Nippon Soda Co., Ltd.), etc. As terminal carboxylic acid group types, for example, there are C-1000 (20-30mers: number average molecular weight of about 1400) (manufactured by Nippon Soda Co., Ltd.), etc. As the terminal hydroxyl type, there are, for example, G-1000 (20-30mer: number average molecular weight of about 1500), G-2000 (30-40mer: number average molecular weight of about 2000), G-3000 (45-60mer: number average molecular weight of about 2900) (all manufactured by Nippon Soda Co., Ltd.), Poly bd R-15HT (20-25mer: number average molecular weight of about 1200), Poly bd R-45HT (45-55mer: number average molecular weight of about 2800) (all manufactured by Idemitsu Kosan Co., Ltd.), etc. One or more kinds of these polymers can be arbitrarily selected for use.

[0071] The weight average molecular weight of polybutadiene is preferably 2000 to 300000, more preferably 2000 to 230000, further preferably 2000 to 200000, and most preferably 3000 to 10000. When the weight average molecular weight is less than 2000, sufficient defoaming performance may not be exerted. When the weight average molecular weight is greater than 300000, it may be difficult to disperse uniformly in the coating, resulting in problems such as shrinkage and shrinkage cavities, and loss of gloss of the coating film. In addition, the SP value of polybutadiene is more preferably 7.5 to 9.0.

[0072] As the polybutene, a homopolymer of 1-butene or a copolymer of 1-butene and isobutene can be used. Additionally, commercially available polybutene can also be used. As the commercially available polybutene, there are copolymers of 1-butene and isobutene, homopolymers of 1-butene, hydrogenated types, etc. As the copolymer of 1-butene and isobutene, for example, there are LV-7 (4 to 6 mers: number average molecular weight of about 300), LV-50 (6 to 9 mers: number average molecular weight of about 450), LV-100 (8 to 12 mers: number average molecular weight of about 500), HV-15 (9 to 13 mers: number average molecular weight of about 630), HV-35 (10 to 15 mers: number average molecular weight of about 750), HV-50 (12 to 16 mers: number average molecular weight of about 800), HV-100 (16 to 20 mers: number average molecular weight of about 980), HV-300 (23 to 27 mers: number average molecular weight of about 1400), HV-1900 (45 to 55 mers: number average molecular weight of about 2900) (all manufactured by ENEOS Corporation), etc. As the homopolymer of 1-butene, for example, there are 15R (9 to 11 mers: number average molecular weight of about 570), 35R (12 to 14 mers: number average molecular weight of about 720), 100R (16 to 20 mers: number average molecular weight of about 960), 300R (24 to 30 mers: number average molecular weight of about 1500) (all manufactured by Idemitsu Kosan Co., Ltd.). As the hydrogenated type, for example, there are 0H (5 to 7 mers: number average molecular weight of about 350), 5H (6 to 8 mers: number average molecular weight of about 400), 10H-T (7 to 10 mers: number average molecular weight of about 470), 300H (24 to 30 mers: number average molecular weight of about 1500), 2000H (50 to 55 mers: number average molecular weight of about 3000) (all manufactured by Idemitsu Kosan Co., Ltd.), etc. One or more of these polymers can be arbitrarily selected and used.

[0073] The weight average molecular weight of the polybutene is preferably 400 to 50000, more preferably 400 to 20000. When the weight average molecular weight is less than 400, it may not be possible to exhibit sufficient defoaming performance. When the weight average molecular weight is greater than 50000, it may be difficult to be uniformly dispersed in the coating, resulting in problems such as shrinkage, craters, and loss of gloss of the coating film. Additionally, the SP value of the polybutene is more preferably 7.5 to 9.0.

[0074] As the polyisoprene, commercially available ones can be used. As the commercially available polyisoprene, there are terminal hydroxyl types, hydrogenated types, etc. As the terminal hydroxyl type, for example, there is Poly iP (30 to 40 mers: number average molecular weight of about 2500) (manufactured by Idemitsu Kosan Co., Ltd.), etc. As the hydrogenated type, for example, there is EPOL (Japanese: エポ一ル), which is the hydrogenated type of Poly iP (manufactured by Idemitsu Kosan Co., Ltd.), etc. One or more of these polymers can be arbitrarily selected and used.

[0075] The weight average molecular weight of polyisoprene is preferably 2000 to 50000, more preferably 3000 to 20000. When the weight average molecular weight is less than 2000, sufficient defoaming performance may not be achieved. When the weight average molecular weight is greater than 50000, it may be difficult to disperse uniformly in the coating, resulting in problems such as shrinkage and shrinkage cavities, and loss of gloss of the coating film. In addition, the SP value of polyisoprene is more preferably 7.5 to 9.0.

[0076] Examples of the poly-α-olefin include poly(1-hexene), poly(1-octene), poly(1-decene), poly(1-dodecene), and ethylene-propylene copolymers, and one or more of these may be arbitrarily selected and used.

[0077] The weight average molecular weight of the polyalphaolefin is preferably 400 to 100,000, more preferably 400 to 10,000, and further preferably 500 to 5,000. When the weight average molecular weight is less than 400, it is possible that sufficient defoaming performance cannot be exerted. When the weight average molecular weight is greater than 100,000, it is possible that it is difficult to disperse evenly in the coating, resulting in problems such as shrinkage and shrinkage cavities, and loss of gloss of the coating film. In addition, the SP value of the polyalphaolefin is more preferably 7.5 to 9.0.

[0078] In addition, as the polymer (B) of the present invention, in addition to the above-mentioned polymers, for example, polyalkyl (meth) acrylates, copolymers of dibasic acid esters, polyvinyl fatty acids, copolymers of alkyl (meth) acrylates and vinyl fatty acids, polyalkylene glycol derivatives (not having an ethylene glycol portion, a polyethylene glycol portion, or the above-mentioned polyol portion, and having a weight average molecular weight of 400 to 1,000,000) and the like can also be used. Examples of the polyalkyl (meth)acrylate include polymers or copolymers of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, oleyl (meth)acrylate, behenyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. Examples of the copolymer of the dibasic acid ester include polymers or copolymers of monoesters or diesters of maleic acid, and polymers or copolymers of monoesters or diesters of fumaric acid. As polyvinyl fatty acid esters, for example, polymers or copolymers of vinyl acetate, vinyl pivalate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl octanoate, vinyl decanoate, vinyl laurate, vinyl palmitate, vinyl 2-ethylhexanoate, vinyl 2,2-dimethyloctanoate, vinyl neononanoate, vinyl neodecanoate, vinyl neoundecanoate, etc. can be cited. As copolymers of alkyl (meth) acrylates and vinyl fatty acid esters, for example, copolymers composed of a combination of the above (meth) acrylates and the above vinyl fatty acid esters can be cited. With regard to polyalkyl (meth) acrylates, copolymers of dibasic acid esters, polyvinyl fatty acid esters, and copolymers of alkyl (meth) acrylates and vinyl fatty acid esters, monomers other than the above monomers that do not contain ethylene glycol moieties, polyethylene glycol moieties, and polyol moieties can also be copolymerized in an amount of not more than 50 mol % within a range that does not impair defoaming properties and shear resistance. Examples of the polyalkylene glycol derivatives include polypropylene glycol, polybutylene glycol, polypropylene glycol monobutyl ether, polypropylene glycol monostearyl ether, and polypropylene glycol and polybutylene glycol adducts obtained by adding polyhydric alcohols such as glycerol, trimethylolpropane, and sugars, which do not correspond to the nonionic surfactant (A).

[0079] Among the specific examples shown above, polyvinyl alkyl ether, polybutadiene, polybutene, poly-α-olefin, etc. are preferably used in order to improve defoaming properties, coating appearance, shear resistance, and topcoatability.

[0080] <Content>

[0081] The content of the above-mentioned polymer (B) is preferably 10% to 90% by mass when the total mass of all components in the defoamer composition is 100% by mass. By making the content of the polymer (B) 10% to 90% by mass, sufficient defoaming performance can be exerted. In order to further improve the defoaming effect, it is further preferred that the content of the polymer (B) is 20% to 70% by mass.

[0082] (Organic solid particles (C))

[0083] The organic solid particles (C) of the present invention are components for exerting defoaming properties, and are components added to improve the defoaming effect of the defoamer and the shear resistance of the coating. The organic solid particles (C) are selected from materials with a melting point of at least 50°C and solid particles at 25°C. Such organic solid particles (C) are in a solid state in a liquid medium contained in the composition at 25°C. In addition, the organic solid particles (C) are particles with a particle size of 0.1 μm or more when present in the defoamer composition, and particles are selected that will not dissolve in the defoamer composition at 25°C, or the shape of the primary particles thereof changes.

[0084] Here, the "primary particles" in the present invention refer to isolated particles that are not divided into smaller particles even when diluted with a prescribed medium. In addition, as a method for investigating whether the organic solid particles (C) are in a solid state in a liquid medium contained in the defoamer composition at 25°C, it can be determined by a known qualitative method. For example, a method can be cited in which, after dispersing the organic solid particles in a range not exceeding 50% by mass in the liquid medium contained in the composition, the non-flowable components are separated by filtering or centrifuging the dispersion, and then their melting points are measured.

[0085] <Particle shape>

[0086] Organic solid particles (C) are solid particles composed of organic compounds, and particles that will not disperse in water alone are selected. In addition, when the particle size distribution is measured by a laser diffraction / scattering measurement method, the particle size has a peak value in the range of 0.1 to 150 μm. That is, the peak particle size (also called "mode diameter") of the organic solid particles (C) is preferably in the range of 0.1 to 150 μm, more preferably 2 to 150 μm, and further preferably 2 to 50 μm. By making the peak particle size of the organic solid particles (C) within the above range, a defoamer composition with particularly excellent shear resistance can be obtained.

[0087] As the shape of the particle, compared with the shape of a true sphere, it is preferred to have a concavoconvex surface, and more preferably to have porous particles and thorny protrusions. As such a particle, for example, it can also be a cluster (cluster) of particles whose aspect ratio (aspect ratio) of its primary particles is 1.1 to 100. In particular, when using the above-mentioned cluster, a mixed liquid consisting of a defoaming liquid component (for example, a nonionic surfactant (A) and a polymer (B)) and an organic medium (D) can be appropriately maintained on the particle surface, so that the shear resistance is particularly excellent. The aspect ratio of the primary particles can be controlled by appropriately adjusting the temperature when the particles are precipitated / crystallized and grown, and the time to maintain the temperature.

[0088] When the aspect ratio is less than 1.1, it is difficult to form clusters, it is difficult to retain the defoaming liquid component, and it is difficult to obtain excellent shear resistance. On the other hand, when the aspect ratio is greater than 100, it is difficult to retain the defoaming liquid component due to the excessive gaps between the clusters, and it is also difficult to obtain excellent shear resistance in this case. From the viewpoint of further improving the shear resistance, the aspect ratio is more preferably in the range of 1.5 to 50, further preferably in the range of 2.0 to 11, and most preferably in the range of 2.0 to 9.0.

[0089] In the observation of TEM or SEM, the aspect ratio of the above-mentioned primary particles can be calculated by measuring the shape of isolated particles. Specifically, for example, it can be calculated by the following method. After diluting and suspending the particles to be measured in an appropriately volatile organic solvent in which the particles are not dissolved, the particles are dropped onto a grid for TEM observation or a sample holder for SEM observation, etc., and dried and made into an observation sample. At this time, the type of solvent and the amount of dilution are appropriately adjusted to isolate the particles. The sample made using TEM or SEM is set to a magnification that is easy to observe isolated particles, and the shape of the isolated particles is confirmed. In the case where the shape of the particles is regarded as an ellipse, the distance between the minor axis and the major axis is measured respectively, and the value of the major axis / minor axis is calculated. The same measurement is performed for the particles of at least 10 or more, and the average is used as the aspect ratio of the particles. In the case where the particles are fibrous and difficult to be regarded as an ellipse, the median of the measured fiber width is used as the fiber width, and the value of the fiber length / fiber width is calculated. The same measurement is performed for the isolated fibrous particles of at least 10 or more, and the average is used as the aspect ratio of the fibrous particles.

[0090] <Specific example>

[0091] The organic solid fine particles (C) are not particularly limited, but preferably used are solid fine particles of one or more of amide, urea, polyethylene, oxidized polyethylene, acid-modified polyethylene, and hydrogenated castor oil.

[0092] Amides are obtained, for example, by condensation reaction of fatty acids and amines. The conditions of the condensation reaction (reaction temperature, mixing ratio of each component, etc.) can be appropriately set by a known method. For example, fatty acids and amines as raw materials are added to a reaction vessel such as a four-necked flask, and the raw materials are stirred in an inert gas atmosphere (for example, under a nitrogen gas flow, etc.) to prepare a mixture. Afterwards, the mixture of raw materials is heated and subjected to a polycondensation reaction at 150°C to 200°C for 2 to 10 hours to synthesize fatty acid amides. As fatty acids, monocarboxylic acids, dicarboxylic acids, and tricarboxylic acids can be used, and as amines, monoamines, diamines, and triamines can be used.

[0093] As the monocarboxylic acid, for example, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, hydrogenated castor oil fatty acid (a fatty acid having a hydroxyl group such as 12-hydroxystearic acid (hereinafter, referred to as "12-HAS") obtained by saponifying hydrogenated castor oil), saturated aliphatic monocarboxylic acids such as arachidic acid and behenic acid (docosanoic acid), and unsaturated aliphatic monocarboxylic acids such as oleic acid, linoleic acid, ricinoleic acid, linolenic acid, eicosenoic acid, erucic acid, and mixed fatty acids obtained from natural oils and fats (tall oil fatty acid, rice bran fatty acid, soybean oil fatty acid, tallow fatty acid, etc.) can be used. Among these monocarboxylic acids, in order to improve the defoaming property and shear resistance of the water-based coating, it is preferred that the monocarboxylic acid contain at least a hydroxy fatty acid such as 12-HSA. That is, as the amide used as the organic solid fine particles (C) of the present invention, an amide in which at least one of the fatty acids is a hydroxy fatty acid is preferred.

[0094] As the dicarboxylic acid, for example, a dicarboxylic acid having 4 to 44 carbon atoms can be used, and as such dicarboxylic acid, for example, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, dimer acid, etc. Dimer acid is a polymerized fatty acid obtained by polymerizing (dimerizing) an unsaturated fatty acid (for example, an unsaturated fatty acid having 18 or 22 carbon atoms) obtained from a vegetable oil such as soybean oil, tall oil, linseed oil, and cottonseed oil, and generally, dimer acid having 36 or 44 carbon atoms is commercially available.

[0095] As the tricarboxylic acid, for example, a tricarboxylic acid having 4 to 54 carbon atoms can be used, and examples of such tricarboxylic acids include trimer acid and trimesic acid. Trimer acid is a polymerized fatty acid obtained by distilling and refining dimer acid to increase the trimer acid content, and usually, trimer acid having 54 carbon atoms is commercially available.

[0096] Examples of the monoamine include ethylamine, monoethanolamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, decylamine, laurylamine, myristicamine, cetylamine, stearylamine, 12-hydroxystearylamine, and behenylamine.

[0097] As the diamine, for example, diamines having 2 to 54 carbon atoms such as aliphatic diamines such as 1,2-diaminoethane (ethylenediamine: EDA), 1,2-diaminopropane (propylenediamine: PDA), 1,4-diaminobutane (tetramethylenediamine: TMDA), 1,6-diaminohexane (hexamethylenediamine: HMDA), 1,8-diaminooctane (octamethylenediamine: OMDA), trimethylhexamethylenediamine, 1,12-diaminododecane (dodecamethylenediamine: DMDA), o-xylylenediamine, m-xylylenediamine (MXDA), p-xylylenediamine (PXDA), aromatic diamines such as diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, and methylenebischloroaniline, and alicyclic diamines such as piperazine, isophoronediamine, and 1,3-diaminomethylcyclohexane can be used.

[0098] As the triamine, for example, a triamine having 2 to 54 carbon atoms, such as an aliphatic triamine such as diethylenetriamine, can be used.

[0099] Furthermore, as the amines used in the synthesis of the amide of the present invention, diamines or triamines derived from polymerized fatty acids as polymerized fatty acid derivatives can also be used. As such polymerized fatty acid derivatives, dimer diamine (DDA) as a dimer acid derivative, trimer triamine (TTA) as a trimer acid derivative, etc. are exemplified. Dimer diamine as a dimer acid derivative is a dimer diamine in which the two terminal carboxyl groups of the above-mentioned dimer acid are substituted with primary aminomethyl or amino groups, and commercially available dimer diamines can be used. In addition, trimer triamine as a trimer acid derivative is a trimer triamine in which the three terminal carboxyl groups of the above-mentioned trimer acid are substituted with primary aminomethyl or amino groups, and commercially available trimer triamines can be used.

[0100] Each compound used as the above-mentioned fatty acids and amines can be arbitrarily selected and used alone or in combination of two or more.

[0101] Here, from the viewpoint of further improving the shear resistance, it is preferred that the amide is a diamide. The diamide can be obtained by reacting a fatty acid with a diamine, or by reacting a monoamine with a dicarboxylic acid. Among the diamides, it is more preferred to react the following fatty acids with the following diamines to obtain a fatty acid diamide. The fatty acids used for the synthesis of the fatty acid diamide are selected from the group consisting of alkyl fatty acids (saturated fatty acids) and hydroxy fatty acids, and contain at least one or more hydroxy fatty acids. In addition, the diamines used for the synthesis of the above-mentioned fatty acid diamide include one or more diamines selected from the group consisting of alkylenediamines having 2 to 6 carbon atoms and meta-xylylenediamine. Among these fatty acid diamides, by using ethylenebis-12-hydroxystearic acid diamide, 1,4-butanebis-12-hydroxystearic acid diamide, hexamethylenebis-12-hydroxystearic acid diamide, etc. as organic solid particles (C), the water-based coating containing the defoamer of the present invention can have particularly excellent shear resistance.

[0102] Urea is a polymer, oligomer, diurea, or monourea having a urea bond obtained by the reaction of an isocyanate compound and an amine compound. As the isocyanate compound and the amine compound, one or more of them can be arbitrarily selected from the compounds described below.

[0103] As the isocyanate compound, for example, aromatic monoisocyanate, aliphatic monoisocyanate, alicyclic monoisocyanate, a compound in a form in which these monoisocyanates are made non-volatile and the toxicity is reduced, aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate, a compound in a form in which these diisocyanates are made non-volatile and the toxicity is reduced, adducts such as biuret, uretdione, isocyanurate, and urethane of these diisocyanates, relatively low molecular weight urethane prepolymers, etc. can be used. As the aromatic diisocyanate, for example, toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), m-xylene diisocyanate (MXDI), etc. can be cited. As the aliphatic diisocyanate, for example, hexamethylene diisocyanate (HDI), etc. can be cited. As the alicyclic diisocyanate, for example, isophorone diisocyanate (IPDI), hydrogenated MDI, etc. can be cited. As the polyisocyanate, commercially available products can also be used. As the commercially available products, for example, Aquanate 130, Aquanate 140, Aquanate 200, and Aquanate 210 (manufactured by Tosoh Corporation), Bayhydur 304, Bayhydur XP-2655, Bayhydur 401-70, Bayhydur 3100 (manufactured by Covestro Urethane), BURNOCK DNW-5000, BURNOCK DNW-5500, BURNOCK DNW-6000 (manufactured by DIC Corporation), RESAMIN D-1063, RESAMIN D-2040 (manufactured by Dainichi Seika Kogyo Co., Ltd.), etc. can be cited.

[0104] The amine compound contains a primary amine or a polyamine.

[0105] As the monoamine, for example, aliphatic monoamine, alicyclic monoamine, aromatic monoamine, alkanolamine, etc. can be used. As the aliphatic monoamine, for example, alkyl monoamine, other aliphatic monoamines, etc. can be mentioned. As the alkyl monoamine, for example, octylamine, dodecylamine, octadecylamine, octadecylamine, etc. can be mentioned. As the alicyclic monoamine, for example, cyclohexylamine, etc. can be mentioned. As the aromatic monoamine, aniline, toluidine, etc. can be mentioned. As the alkanolamine, for example, ethanolamine, 2-amino-2-methyl-1-propanol, 12-hydroxystearylamine, etc. can be used.

[0106] As the polyamine, for example, aliphatic polyamine, alicyclic polyamine, aromatic polyamine, etc. can be used. As the aliphatic polyamine, for example, alkylene polyamine, polyalkylene polyamine, other aliphatic polyamine, etc. can be mentioned. As the alkylene polyamine, for example, diaminomethane (methylenediamine), 1,2-diaminoethane, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, etc. can be mentioned. As the polyalkylene polyamine, for example, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenetetramine, etc. can be mentioned. Examples of other aliphatic polyamines include tetrakis(aminomethyl)methane, tetrakis(2-aminoethylaminomethyl)methane, 1,3-bis(2'-aminoethylamino)propane, triethylene-bis(trimethylene)hexylamine, bis(3-aminoethyl)amine, bishexamethylenetriamine, polyethyleneimine, etc. Examples of alicyclic polyamines include 1,4-cyclohexanediamine, 4,4'-methylenebiscyclohexylamine, 4,4'-isopropylidenebiscyclohexylamine, norbornanediamine, bis(aminomethyl)cyclohexane, diaminodicyclohexylmethane, isophoronediamine, and menthanediamine (MDA). Examples of the aromatic polyamine include bis(cyanoethyl)diethylenetriamine, o-xylylenediamine, m-xylylenediamine, p-xylylenediamine, phenylenediamine, naphthalenediamine, diaminodiphenylmethane, diaminodiethylphenylmethane, 2,2-bis(4-aminophenyl)propane, 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenyl sulfone, 2,2'-dimethyl-4,4'-diaminodiphenylmethane, 2,4'-diaminobiphenyl, 2,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, bis(aminomethyl)naphthalene, and bis(aminoethyl)naphthalene.

[0107] Oxidized polyethylene is a wax obtained by oxidizing polyethylene to introduce polar groups. Acid-modified polyethylene is a polyethylene obtained by grafting an unsaturated carboxylic acid or an anhydrous substance thereof.

[0108] Hydrogenated castor oil (also called "solidified castor oil") is a triglyceride of saturated fatty acids obtained by hydrogenating castor oil. Commercially available products can be used as hydrogenated castor oil, and examples of commercially available products include C-wax (manufactured by Kokura Synthetic Industry Co., Ltd.), Kao Wax 85P (manufactured by Kao Corporation), castor solidified oil A (manufactured by Ito Oil Products Co., Ltd.), castor solidified oil (manufactured by Sankei Sangyo Co., Ltd.), etc.

[0109] In addition, as the organic solid particles (C) of the present invention, in addition to the examples mentioned above, for example, polyalkyl (meth) acrylates, copolymers of dibasic acid esters, copolymers of alkyl (meth) acrylates and fatty acid vinyl esters (however, they are in a solid state in the defoamer composition at 25°C (that is, they do not belong to the nonionic surfactant (A) and the polymer (B))) and the like can also be used.

[0110] Among the specific examples described above, ethylenebis(12-hydroxystearic acid) diamide, 1,4-butanebis(12-hydroxystearic acid) diamide, hexamethylenebis(12-hydroxystearic acid) diamide, etc. are preferably used in order to improve defoaming properties and shear resistance.

[0111] <Content>

[0112] When the total mass of all components in the defoamer composition is 100 mass%, the content of the above-mentioned organic solid particles (C) is preferably 0.1 mass% to 10 mass%. By making the content of the organic solid particles (C) 0.1 mass% to 10 mass%, sufficient defoaming and shear resistance can be exerted. In order to further improve the appearance of the coating film obtained by adding the water-based coating composition of the defoamer composition, it is further preferred that the content of the organic solid particles (C) is 1 mass% to 5 mass%.

[0113] (Organic medium (D))

[0114] The organic medium (D) of the present invention is a component for exerting defoaming property together with the nonionic surfactant (A) and the polymer (B) and is a component added to improve the diffusibility of the defoaming agent in the foam film.

[0115] <Liquidity>

[0116] As the organic medium (D), a medium that is liquid at 25° C. other than water having no hydrophilic part in the molecule can be used. In addition, as the organic medium (D), an organic medium having a weight average molecular weight of less than 400 can be selected. By using such a medium, the diffusibility of the defoaming agent of the present invention in the foam film can be improved.

[0117] <Specific example>

[0118] As the organic medium (D), for example, one or more selected from the group consisting of hydrocarbon oils, alcohols, glycol ethers and glycol esters (not included in the nonionic surfactant (A) and the polymer (B)) can be preferably used.

[0119] As the hydrocarbon oil, for example, a hydrocarbon oil selected from the group consisting of the general formula C n H 2n+2 The normal paraffins and isoparaffins represented by C n H 2n One or more cycloalkanes represented by .

[0120] As the above general formula C n H 2n+2 An example of the normal paraffin represented by the invention includes normal hexane, normal heptane, normal octane, normal decane, normal dodecane, liquid paraffin, etc., and further, a normal commercially available normal paraffin system mixed solvent can also be used. As a commercially available product of the normal paraffin system mixed solvent, for example, there is solvent No. 0 L (ENEOS Co., Ltd.), etc. It is also possible to arbitrarily select and use one or more than two of them.

[0121] As the above general formula C n H 2n+2 An example of isoparaffin represented by the invention includes isohexane, isooctane, isododecane, isohexadecane, etc., and further, a commercially available isoparaffin mixed solvent can also be used. In addition, as a commercially available product of an isoparaffin mixed solvent, for example, there are IP solvent, Merveille 30 (manufactured by Idemitsu Kosan Co., Ltd.), ShellSol T series (manufactured by Shell Chemicals), Isopar series (manufactured by ExxonMobil Corporation), etc. It is also possible to arbitrarily select and use one or more than two of them.

[0122] As the above general formula C n H 2n As an example of cycloalkane represented by the invention, commercially available cycloalkane (naphthene) solvents can be used. As commercially available products of cycloalkane solvents, for example, there are methylcyclohexane, ethylcyclohexane, SWA Clean 150 (another name: a mixture of C9 and C10 alkylcyclohexanes) (the above are manufactured by Maruzen Petrochemical Co., Ltd.), Naphthesol series, CACTUS solvent series (the above are manufactured by ENEOS Co., Ltd.), etc. One or more of these can be arbitrarily selected for use.

[0123] In addition, as the organic medium (D), it is also possible to use a mixture of the general formula C used in the present invention from the outset. n H 2n+2 The normal paraffins and isoparaffins represented by C n H 2n Examples of such solvents include Naphthesol M (cycloalkane / isoalkane / normal paraffin = 70% or more / 5 to 10% / 15% or less, a trade name of ENEOS Co., Ltd.), Isosol 300 (a trade name of ENEOS Co., Ltd.), Isosol 400 (a trade name of ENEOS Co., Ltd.), EXXSOL D80 (a trade name of ENEOS Co., Ltd.), and VIZOOL D700 (a trade name of ENEOS Co., Ltd.). (a mixed solvent of paraffin and cycloalkane, a trade name of ExxonMobil Corporation), EXXSOL D110 (a mixed solvent of paraffin and cycloalkane, a trade name of ExxonMobil Corporation), EXXSOL D130 (a mixed solvent of paraffin and cycloalkane, a trade name of ExxonMobil Corporation), EXXSOL D160 (a mixed solvent of paraffin and cycloalkane, a trade name of ExxonMobil Corporation), etc. One or two or more kinds thereof may be arbitrarily selected and used.

[0124] As alcohols, for example, ethanol, n-propanol, isopropanol (IPA), n-butanol, sec-butanol, tert-butanol, 2-ethylhexanol, isostearyl alcohol, oleyl alcohol, texanol (2,2,4-Trimethyl-1,3-pentanediolmonoisobutyrate), etc. can be used. As glycol ethers, for example, ethylene glycol monobutyl ether (butyl glycol), ethylene glycol mono-2-ethylhexyl ether (2-ethylhexyl glycol), diethylene glycol monomethyl ether (methyl diglycol), diethylene glycol dimethyl ether (dimethyl diglycol), triethylene glycol monomethyl ether (HLB: 18), propylene glycol monomethyl ether, propylene glycol n-propyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, etc. can be used. As glycol esters, for example, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, etc. can be used.

[0125] Furthermore, as the organic medium (D), in addition to the above, aromatic solvents such as xylene and toluene, ketone solvents such as methyl isobutyl ketone (MIBK), methyl ethyl ketone (MEK), methyl amyl ketone (MAK: also called 2-heptanone), ether solvents such as cyclopentyl methyl ether, acetates, ester solvents such as ethyl 3-ethoxypropionate, dimethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, etc., amide solvents, polyethers, oils and fats, polyalkylene glycol derivatives (not included in the nonionic surfactant (A) and the polymer (B)), etc. can also be used.

[0126] <Content>

[0127] The content of the organic medium (D) is preferably 0.5% to 70% by mass when the total mass of all components in the defoamer composition is 100% by mass. By making the content of the organic medium (D) 0.5% to 70% by mass, sufficient defoaming performance can be exerted. In order to further improve the defoaming effect, it is further preferred that the content of the organic medium (D) is 5% to 50% by mass.

[0128] (Other optional ingredients)

[0129] The defoamer composition of the present invention is intended to impart other functions, and may also contain other components other than the components shown above and other than the silicone compound within the scope that does not impair the characteristics of the present invention. For example, solvents, surfactants, amphiphilic compounds, etc., or coating additives other than defoamers may be added for the purpose of uniformly dissolving or dispersing the above-mentioned components (A) to (D) or improving the leveling and uniformity of the coating to which the defoamer is added. Specifically, water, nonionic surfactants, ionic surfactants, leveling agents, dispersants, etc. can be cited (however, they are not included in the above-mentioned nonionic surfactants (A), polymers (B), organic solid particles (C), and organic media (D)).

[0130] (Components not included in the defoamer composition of the present invention)

[0131] The defoamer composition of the present invention preferably does not contain a silicone compound (a synthetic polymer having a main skeleton based on a siloxane bond). When a silicone compound is contained in the defoamer composition of the present invention, it is possible that the silicone component bleeds onto the surface of the coating film, causing shrinkage or hindering the surface coating. Thus, when a silicone compound is contained in the defoamer composition of the present invention, it is possible to cause an adverse effect on the appearance of the coating film coated with a water-based paint containing the defoamer composition. Therefore, in a preferred embodiment of the defoamer composition of the present invention, a silicone compound is not contained.

[0132] (Form of Defoaming Agent Composition)

[0133] Specifically, the form of the defoaming agent composition of the present invention includes a suspension in which organic solid particles (C) are suspended, and an oily suspension is dispersed in a medium mainly composed of water (O (suspension) / W type emulsion), a form in which droplets mainly composed of water are dispersed in an oily suspension (W / O (suspension) type emulsion), and a form in which the above-mentioned W / O (suspension) type emulsion is further dispersed in a medium mainly composed of water (W / O (suspension) / W type emulsion).

[0134] (Method for producing defoaming agent composition)

[0135] The method for manufacturing the defoamer composition containing the above-mentioned components is not particularly limited, but in order to make the manufacture of the defoamer composition uniformly dispersed easy and exhibit excellent defoaming properties, it is preferred to prepare a preliminary dispersion of organic solid particles (C) (hereinafter referred to as "particle preliminary dispersion"). And add these to the mixture of the components. It is preferred to add the particle preliminary dispersion while stirring with a disperser or the like. The stirring speed and stirring temperature can be appropriately set according to the dispersion state of the organic solid particles (C). The method for preparing the particle preliminary dispersion is not particularly limited and can be prepared by a method known to those skilled in the art. As such a method, for example, it is known that the organic solid to be used as the particles of the organic solid particles (C) is melted at a predetermined temperature, and the above-mentioned molten liquid is flowed into a container filled with an organic medium (D), thereby precipitating the organic solid particles (C) while cooling in the organic medium (D), and a method of heating the organic solid particles (C) adjusted to a predetermined particle size while suspending them in the organic medium (D).

[0136] (Application of defoamer composition)

[0137] The defoamer composition of the present invention is not particularly limited in its application as long as it is added to water-based paint, but is particularly preferably used for applications requiring high appearance and coating systems of multilayer coatings. For example, when the defoamer composition of the present invention is used, it can impart sufficient defoaming properties during the manufacture, coating and drying of automobile water-based base coatings, automobile water-based mid-coating coatings, automobile water-based primer coatings, high-end furniture water-based coatings, floor coatings, building interior and exterior coatings, anti-corrosion coatings, home appliances, etc., and prevent the occurrence of coating defects such as solvent popping in the sintering process. In addition, the defoamer composition of the present invention can also be preferably used in the case of using coating raw materials that are difficult to disperse in water, and in the case of recycling the coating in order to prevent the sedimentation and separation of the components in the coating.

[0138] (Effect presentation mechanism)

[0139] The mechanism of defoaming of defoaming droplets and hydrophobic particles is well known to those skilled in the art. For example, it is described as follows. Defoaming droplets and hydrophobic particles invade the bubble film, and when the bubble film thickness decreases with the drainage in the bubble film, the defoaming components contained in the defoaming droplets and hydrophobic particles penetrate the bubble film. Next, the defoaming components that penetrate are highly hydrophobic, so water breaks bubbles in order to avoid the defoaming components. Since hydrophobic particles have a minimum affinity with water-based coatings, there are many cases of using them in combination with surfactants, but under high shear and long-term shearing, the surfactant is separated from the hydrophobic particles and the hydrophobic surface is exposed. Therefore, the hydrophobic particles cannot stably exist in the water-based coating and condense. The condensed hydrophobic particles will not be dispersed again, resulting in coarsening, etc., or the effective particle concentration is reduced, resulting in the disappearance of the defoaming effect. In addition, it can be considered that the defoaming droplets are gradually refined by shear force, and the defoaming effect is lost when the size of the degree of penetrating the bubble film cannot be maintained.

[0140] On the other hand, in the defoamer composition of the present invention, the hydrophobic organic solid particles (C) are present in the defoaming droplets composed of the nonionic surfactant (A), the defoaming polymer (B) and other defoaming components. In this regard, the conventional composite defoamer is also in the same form. However, since the organic solid particles (C) in the present invention are organic substances with high affinity to the defoaming component, the defoaming component is kept on the particle surface, thereby preventing the hydrophobic surface of the particles from being exposed due to shear force. In addition, even when the organic solid particles (C) fly out of the defoaming droplets, since a small amount of defoaming liquid remains on the particle surface, they are quickly protected by the nonionic surfactant (A) and colloidized, suppressing the aggregation of the organic solid particles (C), and the protected colloided organic solid particles (C) are placed in the defoaming droplets again, thereby being able to return to the form with excellent defoaming effect. According to this mechanism, it can be considered that even when the water-based coating to which the defoamer is added is exposed to high shear, and when it is exposed to long-term shear, the defoaming droplets are miniaturized, or the hydrophobic particles fly out from the defoaming droplets, the droplets with defoaming effect can be reconstructed again around the protective colloided particles, and the defoaming effect can be maintained. In order to construct this mechanism, appropriate selection and combination of materials of nonionic surfactant (A), polymer (B) and organic solid particles (C) are required. For the imparting of shear resistance of the above mechanism, it is further preferred that the shape of the organic solid particles (C) has specific characteristics. Specifically, it can be considered that (1) in the case of porous particles, (2) in the case of particles having a concave-convex surface, (3) in the case of clusters of microcrystals with a specific aspect ratio, more excellent shear resistance is shown.

[0141] [Water-based coating composition]

[0142] The water-based coating composition of the present invention contains the above-mentioned defoamer composition and water-based resin as essential components. In addition, the water-based coating composition of the present invention may further contain other coating raw materials such as diluent solvent, pigment, dispersant, lubricant, emulsifier, viscosity modifier, film-forming aid, pH adjuster, etc. as optional components.

[0143] (Defoamer content)

[0144] The content of the defoamer composition of the present invention varies according to the type of water-based resin as a binder (binder) in the water-based coating composition, the deployment composition of the pigment, etc., but, generally, relative to the water-based coating composition, it is preferably 0.1% by mass to 5% by mass, and more preferably 0.5% by mass to 2% by mass. When the content of the defoamer composition is less than 0.1% by mass, it is possible that the addition effect of the defoamer composition of the present invention such as defoaming property and shear resistance cannot be fully exerted. On the other hand, when the content of the defoamer composition is greater than 5% by mass, the interlayer adhesion deteriorates when the coating is repeatedly applied, or the adverse effects of uneven application in the topcoat coating film, or the possibility of deterioration of the water resistance of the coating film after drying, are not preferred.

[0145] (Water-based resin)

[0146] The water-based resin contained in the water-based coating composition of the present invention as a bonding agent is a resin component dispersed in a medium with water as the main body. As a resin component, for example, acrylic resin, acrylic silicone resin, alkyd resin, polyester resin, urethane resin, epoxy resin, silicone resin, fluororesin, etc. can be cited. As the form of water-based resin, it is divided into water-soluble, colloidal dispersion liquid, and emulsion according to the dispersion form, but no matter what form is applicable. These resins can be, for example, heat-cured, ultraviolet-cured, electron-beam-cured, oxidative-cured, photocation-cured, peroxide-cured, and resins cured by chemical reactions in the presence or absence of catalysts, or resins that are high in glass transition point and do not accompany chemical reactions and only become coatings by volatilizing diluents. In addition, as a curing agent, for example, amino resins, melamine resins, isocyanate compounds, blocked isocyanate compounds, silane coupling agents, and epoxy compounds, etc. can be cited.

[0147] (pigment)

[0148] Examples of the pigment include body pigments such as calcium carbonate (heavy calcium carbonate (GCC), precipitated calcium carbonate (PCC), etc.), barium sulfate, silicon dioxide, aluminum hydroxide, talc, mica, organic fiber, glass powder, etc.; coloring pigments such as titanium dioxide, carbon black, chrome yellow, cadmium yellow, ochre, titanium yellow, zinc chromate, red iron oxide, aluminosilicate, quinacridone, phthalocyanine, anthraquinone, dione pyrrolopyrrole, benzimidazolone, and isoindolinone; and metallic pigments such as aluminum flake powder, copper flake powder, mica-like iron oxide, mica, and flaky powders of mica coated with metal oxides.

[0149] (Other additives)

[0150] The water-based coating composition of the present invention may contain other substances, for example, dispersants, lubricants, emulsifiers, viscosity modifiers, dehydrating agents (for example, silane coupling agents), adhesion promoters, surfactants, curing catalysts, film-forming aids, desiccants, antifouling agents, sensitizers, antioxidants, light stabilizers, ultraviolet absorbers, water-resistant agents, antiseptics and mildew preventers, leveling agents, flame retardants, antistatic agents, release agents, deodorants, pH adjusters, fragrances and other additives, within the scope of not impairing its characteristics and the purpose of the present invention.

[0151] Here, as a dispersant for dispersing pigments in coatings, a wetting agent for improving the wetting and smoothness of pigments, an emulsifier for emulsifying non-aqueous resins, a viscosity modifier for controlling the fluidity of coatings, etc., surfactants are usually used to generate unnecessary bubbles during the manufacturing process and coating of water-based coatings. However, by making the water-based coating composition contain the defoamer composition of the present invention, the generation and residue of bubbles can be suppressed, or even when a high shear force is applied to the coating, excellent defoaming properties can be maintained. As a result, a coating film with excellent coating appearance can be formed, and top coating properties will not be hindered.

[0152] (Method for producing water-based coating composition)

[0153] The water-based coating composition of the present invention can be manufactured according to a known method for manufacturing water-based coatings. For example, the above-mentioned defoamer composition and components other than the pigment are stirred and mixed in a medium mainly composed of water such as ion-exchanged water, and then pH is adjusted as needed to prepare a clear coating. The defoamer composition and the pigment are added to the clear coating and dispersed in the clear coating, thereby manufacturing the water-based coating composition.

[0154] In addition, the timing of adding the defoamer composition of the present invention to the water-based paint may be during the process of mixing the pigment as described above, or may be added after the water-based paint is manufactured, or may be added as a master batch. In addition, the equipment used for dispersing the defoamer composition and the pigment may be equipment commonly used in the manufacture of water-based paints. Furthermore, the stirring speed and stirring time conditions during the dispersion of the defoamer composition and the pigment are not particularly limited, and may be appropriately set while confirming the dispersion state of the defoamer composition and the pigment.

[0155] (Application of water-based coating composition)

[0156] The water-based coating composition of the present invention is particularly preferably used for applications requiring high appearance and coating systems of multi-layer coatings. Such applications include, for example, coating of automotive materials, coating of high-end furniture materials, floor coatings, coatings for interior and exterior building decorations, anti-corrosion coatings, and coating of household appliances. In addition, the water-based coating composition of the present invention can also be preferably used in applications such as when using coating raw materials that are difficult to disperse in water, and when preventing the sedimentation of components in the coating and separating and recycling the coating.

[0157] [thing]

[0158] The article of the present invention is an article in which the surface of a substrate as a coated object is covered with a coating agent containing the above-mentioned defoaming agent composition. That is, the article of the present invention is composed of a substrate and a coating film obtained by covering the surface of the substrate with the coating agent.

[0159] (Base material)

[0160] The substrate of the article of the present invention is not particularly limited, and examples thereof include substrates made of metal, plastic, wood, rubber, glass, stone, cement, mortar, paper, nonwoven fabric, cloth, and ceramics.

[0161] (Coating)

[0162] The coating film possessed by the article of the present invention is, for example, obtained by curing the above-mentioned water-based coating composition after applying it to the above-mentioned substrate. The coating film formed on the surface of the substrate may be a single-layer coating film or a coating film formed by laminating multiple coating films. The water-based coating composition containing the defoamer composition of the present invention has excellent defoaming properties and shear resistance, so even when the water-based coating composition is used for purposes requiring extremely high appearance and topcoat properties, a satisfactory appearance of the coating film can be obtained without hindering topcoat properties.

[0163] (Coating agent)

[0164] Examples of the coating agent of the present invention used for coating the above-mentioned substrate include the above-mentioned water-based coating composition.

[0165] (How to make the item)

[0166] The article of the present invention can be manufactured by applying a coating agent such as the water-based coating composition of the present invention to the above-mentioned substrate, followed by drying and curing. The coating method of the coating agent is not particularly limited, and for example, spraying, roller coating, brush coating, curtain coating, rod coating, scraper method, slot coating, dip coating, flow coating, etc. can be cited. The curing method of the coating agent is not particularly limited, and for example, room temperature curing, heat curing, ultraviolet curing, etc. can be cited.

[0167] In addition, when a plurality of coating films (multilayer coating films) are formed to the article of the present invention, for example, a coating film (primer coating film) obtained by applying the water-based coating composition of the present invention to a substrate and a topcoat coating film laminated on all or part of the surface of the coating film are included. The coating of the topcoat has the situation of using the same coating as the coating for the primer coating film, and also has the situation of using different coatings. In addition, when forming a multilayer coating film, there is the situation of topcoating after the primer coating is completely dried or cured, and there is also the situation of topcoating in the state of incomplete drying or curing in the range where the primer coating is not disturbed by the topcoat coating. The water-based coating composition containing the defoamer composition of the present invention is excellent in topcoatability, so even when the water-based coating composition is used for the purpose of requiring extremely high appearance and topcoatability, the coating obtained by the water-based coating composition and the interlayer adhesion of the topcoat coating are excellent.

[0168] In the case of forming a multilayer coating in the article of the present invention, the multilayer coating is formed by, for example, applying the whole or part of the surface of the coating obtained by curing the bottom coating water-based coating added with the defoamer composition of the present invention with a top coating. Alternatively, the bottom coating water-based coating added with the defoamer composition of the present invention may not be cured, and after the top coating is wet-covered wet (wet on wet) applied, the bottom coating and the top coating are cured simultaneously. At this point, preferably, after the bottom coating water-based coating added with the defoamer composition of the present invention is applied, natural drying, blowing or preheating and drying are implemented as required, thus the bottom coating water-based coating is not cured and after removing unnecessary solvent (volatile matter of water and organic solvents, etc.), the top coating is applied. As the drying method of the bottom coating water-based coating, preheating and drying are particularly preferred.

[0169] The coating method and curing method of the top coating are not particularly limited, and the same methods as those described above can be used.

[0170] (Purpose of the item)

[0171] The article of the present invention is particularly preferably used in applications requiring high appearance and coating systems of multilayer coating films. Examples of such applications include automobile parts, high-end furniture, and household appliances.

[0172] The preferred embodiments of the present invention are described above, but the present invention is not limited to the above-mentioned embodiments. That is, other embodiments or various modifications that can be thought of by those skilled in the art within the scope of the invention described in the claims are also understood to belong to the technical scope of the present invention.

[0173] Specifically, the invention includes the following.

[0174] (1) A defoamer composition for water-based coatings, characterized in that it contains: a nonionic surfactant (A) having at least one hydrophilic portion selected from the group consisting of an ethylene glycol portion, a polyethylene glycol portion and a polyol portion in the molecule, and an HLB of 1 to 16; a polymer (B) having no hydrophilic portion in the molecule, an SP value of 7.5 to 12, and a weight average molecular weight of 400 to 1,000,000; and organic solid particles (C) in a solid state in the defoamer composition at 25°C.

[0175] (2) The defoaming agent composition according to (1), characterized in that the nonionic surfactant (A) is one or more selected from the group consisting of ethylene glycol fatty ethers, polyoxyalkylene fatty ethers, polyoxyalkylene aromatic ethers, polyoxyalkylene fatty acid esters, oxyalkylene addition derivatives of castor oil, oxyalkylene addition derivatives of hydrogenated castor oil, polyoxyalkylene polyol ethers, polyol fatty acid esters, oxyalkylene addition derivatives of polyol fatty acid esters, polyoxyalkylene alkylamides, acetylene glycols and their derivatives, oxyalkylene addition derivatives of acetylene glycols, polyoxyethylene-polyoxypropylene block copolymers, and polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers.

[0176] (3) The defoamer composition according to (1) or (2), characterized in that the polymer (B) is one or more polymers selected from the group consisting of polyvinyl alkyl ether, polybutadiene, polybutene, polyisoprene, poly-α-olefin, polyalkyl (meth) acrylate, copolymer of dibasic acid ester, polyvinyl fatty acid ester, and copolymer of alkyl (meth) acrylate and vinyl fatty acid ester.

[0177] (4) The defoamer composition according to any one of (1) to (3), characterized in that the organic solid particles (C) are one or more solid particles selected from the group consisting of amide, urea, polyethylene, oxidized polyethylene, acid-modified polyethylene, and hydrogenated castor oil.

[0178] (5) The defoaming agent composition according to (4), characterized in that the amide is a fatty acid diamide obtained by reacting a fatty acid selected from the group consisting of alkyl fatty acids and hydroxy fatty acids and containing at least one hydroxy fatty acid, with a diamine containing one or more diamines selected from the group consisting of alkylenediamines having 2 to 6 carbon atoms and m-xylylenediamine.

[0179] (6) The defoaming agent composition according to any one of (1) to (5), wherein the aspect ratio of the crystals of the organic solid fine particles (C) is 1.1 to 100.

[0180] (7) The defoaming agent composition according to any one of claims (1) to (6), wherein the peak particle size (mode diameter) of the organic solid fine particles (C) is 0.1 to 150 μm.

[0181] (8) The defoaming agent composition according to any one of claims (1) to (7), further comprising an organic medium (D) which is liquid at 25°C other than water which does not contain the hydrophilic part in the molecule, wherein the weight average molecular weight of the organic medium (D) is less than 400.

[0182] (9) The defoaming agent composition according to (8), characterized in that the organic medium (D) is one or more selected from the group consisting of hydrocarbon oils, alcohols, glycol ethers and glycol esters.

[0183] (10) The defoaming agent composition according to any one of claims (1) to (9), which does not contain a silicone compound.

[0184] (11) A water-based coating composition comprising: the defoamer composition according to any one of (1) to (10); and a water-based resin.

[0185] (12) An article characterized by being coated with a coating agent containing the defoaming agent composition according to any one of (1) to (10).

[0186] [Example]

[0187] Hereinafter, the present invention will be specifically described with reference to Examples. In addition, the present invention is not limited to these Examples. In addition, "%" and "part" in the Examples represent "mass %" and "mass part" unless otherwise specified.

[0188] [Preparation of defoamer samples]

[0189] Defoaming agent samples E1 to E54 and C1 to C25 were prepared as follows.

[0190] (Preparation of nonionic surfactant)

[0191] In the present embodiment and comparative example, as the nonionic surfactant component containing the nonionic surfactant (A), the raw materials described in Table 1 as described below were used. In addition, the HLB of the nonionic surfactant is a value obtained by the Griffin method. In addition, the raw material described as "A" as the component type in Table 1 is an example of the nonionic surfactant (A) of the present invention, and the raw material described as "non-A component" is a raw material that does not correspond to the nonionic surfactant (A) of the present invention.

[0192]

Table 1

[0193] Table 1 Raw materials of defoamer samples (non-ionic surfactants)

[0194]

[0195] (Synthesis and preparation of polymers)

[0196] In this example and comparative examples, as the polymer component containing polymer (B), the raw materials described in Table 2 below are used. In addition, the raw material with the component type recorded as "B" in Table 2 is an example of the polymer (B) of the present invention, and the raw material recorded as "non-B component" is a raw material not equivalent to the polymer (B) of the present invention. Hereinafter, the synthesis method of the raw material with the "acquisition source" of "synthesis method described in this application" in Table 2 is shown.

[0197] (Synthesis of PEVE)

[0198] As an example of polymer (B), polyethyl vinyl ether (hereinafter, referred to as "PEVE") is synthesized by the method shown below. After charging 150 parts of toluene and 3 parts of a substance obtained by diluting boron trifluoride diethyl ether complex as a cationic polymerization initiator to 10% with diethyl ether into a 1000 ml reaction vessel equipped with a stirring device, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and heating to 30°C while introducing nitrogen, the following dropping solution (a) is uniformly dropped through the dropping funnel over 120 minutes.

[0199] Dropping solution (a)

[0200] 300 parts of ethyl vinyl ether

[0201] 100 parts of toluene

[0202] Thirty minutes after the dropping of dropping solution (a) is completed, 15 parts of ethanol is added to stop the reaction. After the reaction is completed, the solvent is removed using an evaporator to obtain polymer (PEVE). The weight-average molecular weight of the synthesized polymer is 3000 (SP value: 8.6).

[0203] (Synthesis of acrylic copolymer 1)

[0204] Into a 1000 mL reaction vessel equipped with a stirring device, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, 95.0 parts of butyl acetate and 159.4 parts of dibutyl fumarate were charged. Then, while stirring under a nitrogen stream, the internal temperature was raised to 140 °C (reflux state). As a dropping solution, a mixture consisting of 28.1 parts of dibutyl fumarate, 187.5 parts of ethyl acrylate, 30.0 parts of a 55% solution of 2,2-bis(tert-amylperoxy)butane, and 7.5 parts of 2-ethylhexyl mercaptoacetate was charged into the above dropping funnel. Next, while maintaining the internal temperature of the reaction vessel in the reflux state, the above dropping solution was uniformly added dropwise over 120 minutes. After the addition was completed, the reaction temperature was maintained in the reflux state for 120 minutes to carry out the reaction. After the reaction was completed, the solvent was removed by an evaporator to obtain acrylic copolymer 1. The weight-average molecular weight of the synthesized copolymer was 3500 (SP value: 10.1).

[0205] <Synthesis of poly(vinyl neodecanoate)>

[0206] Into a 1000 mL reaction vessel equipped with a stirring device, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, 104.6 parts of butyl acetate were charged. Then, while stirring under a nitrogen stream, the internal temperature was raised to the reflux state of butyl acetate. As a dropping solution, a mixture consisting of 375.0 parts of vinyl neodecanoate (trade name VeoVa (ベオバ) 10: manufactured by HEXON) and 20.5 parts of a 55% solution of 2,2-bis(tert-amylperoxy)butane was charged into the above dropping funnel. Next, while maintaining the internal temperature of the reaction vessel in the reflux state, the above dropping solution was uniformly added dropwise over 120 minutes. After the addition was completed, the reaction temperature was maintained in the reflux state for 60 minutes to carry out the reaction. After the reaction was completed, the solvent was removed by an evaporator to obtain poly(vinyl neodecanoate). The weight-average molecular weight of the synthesized copolymer was 7900 (SP value: 9.0).

[0207] <Synthesis of acrylic copolymer 2>

[0208] Into a 1000 mL reaction container equipped with a stirring device, a reflux cooler, a dropping funnel, a thermometer, and a nitrogen inlet tube, 197.5 parts of an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) were placed. Then, the internal temperature was raised to 95° C. while stirring under a nitrogen stream. As a dropwise solution, a mixture consisting of 250.0 parts of lauryl methacrylate, 49.4 parts of an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) and 3.1 parts of a 40% solution of tert-butyl peroxy-2-ethylhexanoate was placed in the dropping funnel. Next, while maintaining the internal temperature of the reaction container at 95° C., the dropwise solution was uniformly dropped over 75 minutes. After the dropwise addition was completed, the reaction temperature was maintained at 95° C. for 60 minutes, and then 0.7 parts of a 40% solution of tert-butyl peroxy-2-ethylhexanoate was added and maintained at 95° C. for 45 minutes. Thereafter, the internal temperature of the reaction container was raised to 100° C. and the reaction was carried out for 30 minutes. After the reaction was completed, the heating remainder was adjusted to 50% with an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) to obtain an acrylic copolymer 2. The weight average molecular weight of the synthesized copolymer was 178,900 (SP value: 9.0).

[0209] <Synthesis of Acrylic Copolymer 3>

[0210] Into a 1000 mL reaction container equipped with a stirring device, a reflux cooler, a dropping funnel, a thermometer, and a nitrogen inlet tube, 188.5 parts of an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) were charged. Then, the internal temperature was raised to 95°C while stirring under a nitrogen stream. As a dropwise solution, a mixture consisting of 250.0 parts of lauryl methacrylate, 47.1 parts of an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) and 12.5 parts of a 40% solution of tert-butyl peroxy-2-ethylhexanoate was charged into the dropping funnel. Next, the dropwise solution was uniformly dropped over 75 minutes while maintaining the internal temperature of the reaction container at 95°C. After the dropwise addition was completed, the reaction temperature was maintained at 95°C for 60 minutes, and then 0.7 parts of a 40% solution of tert-butyl peroxy-2-ethylhexanoate was added and maintained at 95°C for 45 minutes. Then, the internal temperature of the reaction container was raised to 100°C and the reaction was carried out for 30 minutes. After the reaction was completed, the remaining heating portion was adjusted to 50% with an isoparaffin solvent (trade name Merveille 30: Idemitsu Kosan Co., Ltd.) to obtain an acrylic copolymer 3. The weight average molecular weight of the synthesized copolymer was 74100 (SP value: 9.0).

[0211] <Synthesis of Acrylic Copolymer 4>

[0212] 350.0 parts of methyl propanediol were charged into a 1000 mL reaction container equipped with a stirring device, a reflux cooler, a dropping funnel, a thermometer and a nitrogen inlet tube. After that, the internal temperature was raised to 120°C while stirring under a nitrogen gas stream. A mixture consisting of 75.0 parts of acrylic acid, 50.0 parts of styrene, 25.0 parts of a 50% solution of tert-amyl peroxy-2-ethylhexanoate and 6.3 parts of 2-ethylhexyl thioglycolate was charged into the dropping funnel as a dropping solution. Next, while maintaining the internal temperature of the reaction container at 120°C, the above-mentioned dropping solution was uniformly dropped over 120 minutes. After the dropwise addition was completed, the reaction temperature was maintained at 120°C for 60 minutes, and then 0.8 parts of a 50% solution of tert-amyl peroxy-2-ethylhexanoate was added, and the reaction was maintained at 120°C for 30 minutes. After the reaction was completed, the solvent was removed by an evaporator to obtain an acrylic copolymer 4. The weight average molecular weight of the synthesized copolymer was 3600 (SP value: 12.4).

[0213] <Synthesis of Acrylic Copolymer 5>

[0214] 200.0 parts of butyl acetate were charged into a 1000 mL reaction container equipped with a stirring device, a reflux cooler, a dropping funnel, a thermometer and a nitrogen inlet tube. After that, the internal temperature was raised to the reflux state of butyl acetate while stirring under a nitrogen gas stream. A mixture consisting of 250.0 parts of ethyl acrylate and 50.0 parts of a 50% solution of tert-amyl peroxy-2-ethylhexanoate was charged into the dropping funnel as a dropwise solution. Next, while the internal temperature of the reaction container was maintained in a reflux state, the dropwise solution was uniformly added dropwise over 100 minutes. After the dropwise addition was completed, the reaction temperature was maintained under reflux for 60 minutes, and then 1.5 parts of a 50% solution of tert-amyl peroxy-2-ethylhexanoate was added dropwise and reacted for 30 minutes. After the reaction was completed, the solvent was removed by an evaporator to obtain an acrylic copolymer 5. The weight average molecular weight of the synthesized copolymer was 3900 (SP value: 10.2).

[0215] <Synthesis of Acrylic Copolymer 6>

[0216] 108.0 parts of butyl acetate were charged into a 1000 mL reaction vessel equipped with a stirring device, a reflux cooler, a dropping funnel, a thermometer and a nitrogen inlet tube. After that, the internal temperature was raised to the reflux state of butyl acetate while stirring under a nitrogen gas stream. A mixture consisting of 375.0 parts of 2-ethylhexyl acrylate and 17.2 parts of a 55% solution of 2,2-di(tert-amylperoxy)butane was charged into the dropping funnel as a dropwise solution. Next, the internal temperature of the reaction vessel was maintained in a reflux state, and the dropwise solution was evenly dropped for 120 minutes. After the dropwise addition was completed, the reaction temperature was maintained for 60 minutes in a reflux state to react. After the reaction was completed, the solvent was removed by an evaporator to obtain an acrylic copolymer 6. The weight average molecular weight of the synthesized copolymer was 7800 (SP value: 9.2).

[0217] The SP values ​​of the polymers shown in Table 2 were calculated by the Fedors method. In addition, when the weight average molecular weight of the polymers shown in Table 2 was measured, HLC-8320GPC (manufactured by Tosoh Corporation) was used as a measuring device, TSKgel GMHxl×2, TSKgel G2500Hxl, TSKgel G2000Hxl, and TSKgel guardcolumn (all manufactured by Tosoh Corporation) were used as chromatographic columns, tetrahydrofuran (THF) was used as a mobile phase, the column temperature was set to 40°C, the flow rate was set to 1 mL / min, and an RI detector was used as a detector. In addition, the weight average molecular weight shown in Table 2 is a value calculated based on the molecular weight of standard polystyrene according to the chromatograph measured by gel permeation chromatography (GPC).

[0218]

Table 2

[0219] Table 2 Raw materials (polymers) of defoamer samples

[0220]

[0221] (Production and preparation of solid particles)

[0222] In the present embodiment and comparative example, as the solid particle component containing organic solid particles (C), the raw materials described in Table 3 as described below are used. In addition, the raw material described as "C" as the component type in Table 3 is an example of the organic solid particles (C) of the present invention, and the raw material described as "non-C component" is a raw material that does not correspond to the organic solid particles (C) of the present invention. The following shows the method for manufacturing the raw material whose "acquisition source" in Table 3 is "manufacturing method described in this application". Specifically, particles OC-1 to OC-18, which are examples of organic solid particles (C), are manufactured by the method shown below.

[0223] <oc-1>

[0224] Under a nitrogen stream, 2 mol of 12-hydroxystearic acid (12-HSA) and 1 mol of hexamethylenediamine were reacted at 190° C. for 6 hours to remove the generated water, thereby obtaining diamide (a1) (step 0). Next, a mixture (microparticle mixture) of 10 parts of diamide (a1) as a microparticle component and 90 parts of Merveille 30 (isoparaffin manufactured by Idemitsu Kosan Co., Ltd.) as an organic medium (D) was heated to 165° C. using a heater, and diamide (a1) was heated and dissolved in Merveille 30 to obtain a microparticle solution (step 1). Separately, 60 parts of Merveille 30 were placed in a 500 mL container, and the microparticle solution was flowed in with stirring, and then cooled so that the temperature after mixing was 97.0° C. (step 2). After the mixed solution into which the microparticle dissolving solution was poured was cooled to about 30°C, 40 parts of ethanol was added to the mixed solution and stirred (step 3). Next, the temperature of the mixed solution was adjusted to 46.5°C while stirring was maintained, and stirring was continued for 12 minutes to obtain a preliminary dispersion of microparticles OC-1 (step 4).

[0225] <oc-2>

[0226] A preliminary dispersion of microparticles OC-2 was obtained by the same method as OC-1, except that in step 0, diamide (a2) was obtained by reacting 2 mol of 12-HSA and 1 mol of ethylenediamine, in step 1, diamide (a2) was used instead of diamide (a1), and the microparticle mixture was heated to 155°C, in step 2, it was cooled so that the temperature after mixing was 88.0°C, and in step 4, the temperature of the mixed solution was adjusted to 48.5°C.

[0227] <oc-3>

[0228] A preliminary dispersion of microparticles OC-3 was obtained by the same method as OC-1, except that in step 0, diamide (a3) ​​was obtained by reacting 2 mol of 12-HSA and 1 mol of 1,4-diaminobutane, in step 1, diamide (a3) ​​was used instead of diamide (a1), and the microparticle mixture was heated to 160°C, in step 2, the mixture was cooled so that the temperature after mixing was 97.0°C, and in step 4, the temperature of the mixed solution was adjusted to 42.0°C.

[0229] <oc-4>

[0230] A preliminary dispersion of fine particles OC-4 was obtained by the same method as OC-3, except that in step 2, the temperature after mixing was cooled to 92.5°C, and in step 4, the temperature of the mixed liquid was adjusted to 45.3°C.

[0231] <oc-5>

[0232] A preliminary dispersion of microparticles OC-5 was obtained by the same method as OC-1, except that solidified castor oil was used instead of diamide (a1), the microparticle mixture was heated to 95°C in step 1, and in step 2, it was cooled so that the temperature after mixing was 53.9°C, and step 4 was not performed.

[0233] <oc-6>

[0234] A preliminary dispersion of particles OC-6 was obtained by the same method as OC-1, except that ethylene glycol monobutyl ether (butyl glycol) was used as the organic medium (D) in steps 1 and 2, the particle mixture was heated to 120° C., and in step 2, it was cooled so that the temperature after mixing was 25.0° C., and step 4 was not performed.

[0235] <oc-7>

[0236] A preliminary dispersion of microparticles OC-7 was obtained by the same method as OC-1, except that a low-density oxidized polyethylene (trade name "AC 629" manufactured by Honeywell Japan Ltd.) was used instead of diamide (a1), the microparticle mixture was heated to 150° C. in step 1, and in step 2, it was cooled so that the temperature after mixing was 46.7° C., and step 4 was not performed.

[0237] <oc-8>

[0238] A preliminary dispersion of fine particles OC-8 was obtained by the same method as OC-1, except that in step 2, the temperature after mixing was cooled to 47.7°C, and in step 4, the temperature of the mixed liquid was adjusted to 38.7°C.

[0239] <oc-9>

[0240] A preliminary dispersion of fine particles OC-9 was obtained by the same method as OC-1, except that in step 2, the temperature after mixing was cooled to 44.7°C, and in step 4, the temperature of the mixed liquid was adjusted to 40.3°C.

[0241] <oc-10>

[0242] A preliminary dispersion of microparticles OC-10 was obtained by the same method as OC-1, except that 2-ethylhexanol was used as the organic medium (D) in steps 1 and 2, the microparticle mixture was heated to 135°C, in step 2, it was cooled so that the temperature after mixing was 51.4°C, and in step 4, the temperature of the mixed solution was adjusted to 57.7°C.

[0243] <oc-11>

[0244] A preliminary dispersion of microparticles OC-11 was obtained by the same method as OC-1, except that 2-ethylhexanol was used as the organic medium (D) in steps 1 and 2, the microparticle mixture was heated to 135°C, in step 2, it was cooled so that the temperature after mixing was 45.5°C, and in step 4, the temperature of the mixed solution was adjusted to 62.1°C.

[0245] <oc-12>

[0246] A preliminary dispersion of microparticles OC-12 was obtained by the same method as OC-1, except that propylene glycol monomethyl ether was used as the organic medium (D) in steps 1 and 2, the microparticle mixture was heated to 110°C, in step 2, it was cooled so that the temperature after mixing was 48.5°C, and in step 4, the temperature of the mixed solution was adjusted to 50.4°C.

[0247] <oc-13>

[0248] A preliminary dispersion of fine particles OC-13 was obtained by the same method as OC-2, except that in step 2, the temperature after mixing was cooled to 37.4°C, and in step 4, the temperature of the mixed liquid was adjusted to 61.3°C.

[0249] <oc-14>

[0250] A preliminary dispersion of microparticles OC-14 was obtained by the same method as OC-1, except that propylene glycol monomethyl ether was used as the organic medium (D) in steps 1 and 2, the microparticle mixture was heated to 110°C, in step 2, it was cooled so that the temperature after mixing was 38.5°C, and in step 4, the temperature of the mixed solution was adjusted to 57.4°C.

[0251] <oc-15>

[0252] After step 3, instead of step 4, the mixed solution obtained in step 3 was placed in a bottle, heated to 70°C over 24 hours, and maintained at this temperature for 24 hours. Thereafter, the temperature was lowered to 25°C over 24 hours, and a preliminary dispersion of fine particles OC-15 was obtained by the same method as OC-1.

[0253] <oc-16>

[0254] After step 3, instead of step 4, the mixed solution obtained in step 3 was placed in a bottle, heated to 80°C over 24 hours, and maintained at this temperature for 24 hours. Thereafter, the temperature was lowered to 25°C over 24 hours, and a preliminary dispersion of fine particles OC-16 was obtained in the same manner as OC-1.

[0255] <oc-17>

[0256] A preliminary dispersion of fine particles OC-17 was obtained by the same method as OC-2, except that in step 2, the temperature after mixing was cooled to 45.6°C, and in step 4, the temperature of the mixed liquid was adjusted to 45.5°C.

[0257] <oc-18>

[0258] A preliminary dispersion of microparticles OC-18 is obtained by the same method as OC-1, except that in step 0, diamide (a4) is obtained by reacting 2 mol of 12-HSA and 1 mol of m-xylylenediamine, in step 1, diamide (a4) is used instead of diamide (a1), and the microparticle mixture is heated to 150°C, in step 2, it is cooled so that the temperature after mixing is 46.5°C, and in step 4, the temperature of the mixed solution is adjusted to 47.3°C.

[0259] <Measurement of Peak Particle Size>

[0260] The peak particle diameter of the fine particles OC-1 to OC-18 obtained as described above was measured using a particle size distribution analyzer Microtrac MT-3000EXII / USVR (manufactured by Microtrac) and Merveille 30 as a circulating solvent. Table 3 shows the peak particle diameter (μm) of each organic solid fine particle.

[0261] <Measurement of Aspect Ratio>

[0262] For the fine particles OC-1 to OC-18 obtained as described above, the aspect ratios were measured as shown in the following 1) to 7).

[0263] 1) The preliminary dispersion of the microparticles OC-1 to OC-18 was diluted 300 times with xylene, and ultrasonic waves were irradiated for 30 seconds to disperse the microparticles in the dilution.

[0264] 2) On the filter paper, add 1 drop of the dilution solution of 1) to a copper microgrid (grid spacing 150 μm) with a carbon reinforced collodion supporting film, and dry naturally.

[0265] 3) The microgrid of the sample carrying the microparticles obtained in 2) is fixed on the SEM holder using carbon tape.

[0266] 4) SEM measurement The measurement was performed under the following conditions: measuring device: SU3500 (manufactured by Hitachi High-Technologies Corporation); measuring mode: high vacuum and low accelerating voltage; image: reflected electron image; imaging magnification: 2,000 times; brightness / contrast: automatic; and focus: manual.

[0267] 5) Image Analysis Using image analysis software (ImageJ), after brightness / contrast correction and smoothing correction, the image was binarized to remove noise, particles at the image boundary, and agglomerated particles, and then particle analysis was performed.

[0268] 6) When the particles to be measured are composed only of non-convex shapes, particle analysis is performed, and the aspect ratio (= major diameter value / minor diameter value) is calculated based on the major diameter value and minor diameter value obtained for each particle. The average of the aspect ratios of more than 10 particles is taken as the aspect ratio of the particle sample (particles OC-1 to OC-18).

[0269] 7) When the particles to be measured contain convex shapes and non-convex shapes, use the Freehandline tool to measure the fiber length, use the Straight line tool to measure the fiber width in the center of the particle, calculate the aspect ratio (= fiber length value / fiber width value), and take the average of the aspect ratios of more than 10 particles as the aspect ratio of the sample.

[0270] In addition, the above-mentioned "non-convex shape" refers to a shape in which the area of ​​the convex hull of the particle (the part surrounded by the shrinkable virtual curve) is more than twice the actual area. In addition, the above-mentioned "convex shape" refers to a shape in which the area of ​​the convex hull of the particle is less than twice the actual area. The aspect ratio of each organic solid particle is shown in Table 3.

[0271]

Table 3

[0272] Table 3 Raw materials of defoamer samples (solid particles)

[0273]

[0274]

[0275] (Preparation of organic medium)

[0276] In the present examples and comparative examples, the raw materials described in Table 4 below were used as the organic medium (D). In addition, Table 4 describes the boiling points of some of the raw materials.

[0277]

Table 4

[0278] Table 4 Raw materials of defoamer samples (organic medium)

[0279]

[0280] (Preparation of defoamer samples)

[0281] Defoamer samples E1 to E54 and C1 to C25 were prepared by the method described below. Details of the preparation method of each defoamer sample are shown below.

[0282] <Defoamer Sample E1>

[0283] Into a 100 mL polycup, EMALEX RWIS-305 (triisostearate PEG-5 hydrogenated castor oil manufactured by Nippon Emulsion Co., Ltd.): 7.5 parts and PEVE: 27.5 parts were charged, and while stirring with a disperser, 30.0 parts of the preliminary dispersion of fine particles OC-1 was added, and then stirred and mixed at 2000 rpm for 15 minutes to obtain a defoamer sample E1.

[0284] <Defoamer Sample E2>

[0285] Defoamer Sample E2 was obtained by the same method as Defoamer Sample E1 except that the preliminary dispersion of fine particles OC-1 was changed to the preliminary dispersion of fine particles OC-2.

[0286] <Defoamer Sample E3>

[0287] Defoamer Sample E3 was obtained by the same method as Defoamer Sample E1 except that the preliminary dispersion of fine particles OC-1 was changed to the preliminary dispersion of fine particles OC-3.

[0288] <Defoamer Sample E4>

[0289] Defoamer Sample E4 was obtained by the same method as Defoamer Sample E1 except that EMALEX RWIS-305 was changed to EMALEX RWIS-330 (PEG-30 triisostearate hydrogenated castor oil manufactured by Nippon Ekuie Co., Ltd.).

[0290] <Defoamer Sample E5>

[0291] Defoamer Sample E5 was obtained by the same method as Defoamer Sample E1 except that EMALEX RWIS-305 was replaced with Blaunon CW-3 (PEG-3 hydrogenated castor oil manufactured by Aoki Oil & Fats Industries, Ltd.).

[0292] <Defoamer Sample E6>

[0293] Defoamer Sample E6 was obtained by the same method as Defoamer Sample E2 except that EMALEX RWIS-305 was changed to Blaunon CW-3 (PEG-3 hydrogenated castor oil manufactured by Aoki Oil & Fats Industries, Ltd.).

[0294] <Defoamer Sample E7>

[0295] Defoamer Sample E7 was obtained by the same method as Defoamer Sample E3 except that EMALEX RWIS-305 was replaced with Blaunon CW-3 (PEG-3 hydrogenated castor oil manufactured by Aoki Oil & Fats Industries, Ltd.).

[0296] <Defoamer samples E8 to E18>

[0297] Defoamer samples E8 to E18 were obtained by the same method as that of the defoamer sample E1, except that EMALEX RWIS-305 was changed to "A: nonionic surfactant" described in Table 6, and the polymer (B) was changed to Duasyn 164.

[0298] <Defoamer Sample E19>

[0299] Defoamer sample E19 was obtained by the same method as defoamer sample E1, except that PEVE: 27.5 parts was changed to PEVE: 10.3 parts and RB810: 3.4 parts, and the polymer (PEVE and RB810) was diluted with Merveille (メルベイユ) 30: 13.8 parts, and then mixed with the preliminary dispersion of EMALEX RWIS-305 and microparticles OC-1.

[0300] <Defoamer Sample E20>

[0301] Defoamer sample E20 was obtained by the same method as Defoamer sample E1, except that PEVE: 27.5 parts was changed to acrylic copolymer 1: 22.0 parts, and the polymer (acrylic copolymer 1) was diluted with 2-ethylhexanol: 5.5 parts before mixing with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-10.

[0302] <Defoamer samples E21, E22, E24 to E26>

[0303] Defoamer samples E21, E22, and E24 to E26 were obtained by the same method as that of the defoamer sample E1 except that PEVE was changed to "B: polymer" described in Table 7.

[0304] <Defoamer Sample E23>

[0305] Defoamer Sample E23 was obtained by the same method as Defoamer Sample E1 except that EMALEX RWIS-305 was replaced by EMALEX RWIS-320 (PEG-20 hydrogenated castor oil triisostearate manufactured by Nippon Ekuie Co., Ltd.) and PEVE was replaced by polyvinyl neodecanoate.

[0306] <Defoamer Sample E27>

[0307] Defoamer sample E27 was obtained by the same method as for defoamer sample E1, except that 27.5 parts of PEVE was replaced with 27.5 parts of Merveille 30 (solvent) solution of acrylic copolymer 2 (polymer concentration: 50 mass%) and mixed with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-1.

[0308] <Defoamer Sample E28>

[0309] Defoamer sample E28 was obtained by the same method as for defoamer sample E1, except that 27.5 parts of PEVE was replaced with 27.5 parts of Merveille 30 (solvent) solution of acrylic copolymer 3 (polymer concentration: 50 mass%) and mixed with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-1.

[0310] <Defoamer Sample E29>

[0311] Defoamer sample E29 was obtained by the same method as defoamer sample E1, except that PEVE: 27.5 parts was changed to LUTONAL I60 (a solvent naphtha solution with a PIBVE concentration of 80% by mass), which is a polyisobutyl vinyl ether (PIBVE) manufactured by BASF: 18.6 parts, and the polymer (LUTONAL 160) was diluted with Merveille 30: 8.9 parts, and then mixed with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-1.

[0312] <Defoamer Sample E30>

[0313] Defoamer sample E30 was obtained by the same method as for defoamer sample E1, except that PEVE: 27.5 parts was changed to LUTONAL I 60 (solvent naphtha solution with a PIBVE concentration of 80% by mass): 11.5 parts, and the polymer (LUTONAL I60) was diluted with Merveille 30: 16.0 parts, and then mixed with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-1.

[0314] <Defoamer Sample E31>

[0315] Defoamer sample E31 was obtained by the same method as defoamer sample E1, except that 27.5 parts of PEVE was changed to 15.3 parts of PIBVE manufactured by Siwei (PIBVE concentration is 60% by mass in isoparaffin solution), and the polymer (PIBVE manufactured by Siwei) was diluted with 12.2 parts of Merveille 30, and then mixed with the prepared dispersion of MALEX RWIS-305 and microparticles OC-1.

[0316] <Defoamer samples E32 to E44>

[0317] Defoamer samples E32 to E44 were obtained by the same method as that of the defoamer sample E1 except that the preliminary dispersion of the fine particles OC-1 was changed to "C: organic solid fine particles (fine particles OC-4 to OC-16)" described in Table 8.

[0318] <Defoamer Sample E45>

[0319] Defoamer sample E45 was obtained by the same method as that of defoamer sample E1, except that PEVE: 27.5 parts was changed to acrylic copolymer 5: 22.0 parts, and the polymer (acrylic copolymer 5) was diluted with 2-ethylhexanol: 5.5 parts before mixing with the preliminary dispersion of EMALEX RWIS-305 and fine particles OC-10.

[0320] <Defoamer samples E46 to E54>

[0321] Defoamer samples E46 to E54 were obtained by the same method as for defoamer sample E1, except that EMALEX RWIS-305 was replaced by "A: nonionic surfactant" recorded in Table 9, PEVE was replaced by "B: polymer" recorded in Table 9, and the preliminary dispersion of microparticles OC-1 was replaced by "C: organic solid microparticles" recorded in Table 9.

[0322] <Defoamer Sample C1>

[0323] Defoamer Sample C1 was obtained by the same method as Defoamer Sample E1 except that Merveille 30 was used instead of the preliminary dispersion of the fine particles OC-1.

[0324] <Defoamer Sample C2>

[0325] Defoamer Sample C2 was obtained by the same method as Defoamer Sample E4 except that Merveille 30 was used in place of the preliminary dispersion of the fine particles OC-1.

[0326] <Defoamer Sample C3>

[0327] Defoamer Sample C3 was obtained by the same method as Defoamer Sample E5 except that Merveille 30 was used in place of the preliminary dispersion of the fine particles OC-1.

[0328] <Defoamer Sample C4>

[0329] Defoamer Sample C4 was obtained by the same method as Defoamer Sample E1 except that Merveille 30 was used instead of EMALEX RWIS-305 and PEVE.

[0330] <Defoamer Sample C5>

[0331] Defoamer Sample C5 was obtained by the same method as Defoamer Sample E2 except that Merveille 30 was used instead of EMALEX RWIS-305 and PEVE.

[0332] <Defoamer Sample C6>

[0333] Defoamer Sample C6 was obtained by the same method as Defoamer Sample E3 except that Merveille 30 was used instead of EMALEX RWIS-305 and PEVE.

[0334] <Defoamer Sample C7>

[0335] As the defoaming agent sample C7, BYK-024 (manufactured by BYK) which is a mixture of silicone, hydrophobic fine particles, and polyethylene glycol was used.

[0336] <Defoamer Sample C8>

[0337] As the defoamer sample C8, Agitan 295 (manufactured by MUNZING CHEMIE GmbH) which is a mixture of hydrocarbon, hydrophobic silica and an alkoxy compound was used.

[0338] <Defoamer samples C9 to C14, C18>

[0339] Defoamer samples C9 to C14 and C18 were obtained by the same method as the defoamer sample E1, except that EMALEX RWIS-305 was changed to "A: nonionic surfactant" or "nonionic surfactant (non-A component)" described in Table 11, and PEVE was changed to "B: polymer" or "polymer (non-B component)" described in Table 11.

[0340] <Defoamer Sample C15>

[0341] Defoamer sample C15 was obtained by the same method as defoamer sample E1, except that PEVE: 27.5 parts was changed to acrylic copolymer 4: 13.8 parts, the polymer (acrylic copolymer 4) was diluted with propylene glycol monomethyl ether: 13.7 parts, and then mixed with the preliminary dispersion of EMALEX RWIS-305 and microparticles OC-1.

[0342] <Defoamer Sample C16>

[0343] Defoamer sample C16 was obtained by the same method as defoamer sample E1, except that EMALEX RWIS-305 was changed to EMALEX RWIS-330 (PEG-30 hydrogenated castor oil triisostearate manufactured by Nippon Emulsion Co., Ltd.), PEVE: 27.5 parts was changed to acrylic copolymer 4: 13.8 parts, the polymer (acrylic copolymer 4) was diluted with propylene glycol monomethyl ether: 13.7 parts, and then mixed with EMALEX RWIS-330 and the prepared dispersion of microparticles OC-1.

[0344] <Defoamer Sample C17>

[0345] 13.0 parts of FS1265-10000cst (fluorine-modified silicone manufactured by Dow Toray Co., Ltd.) was diluted with 32.5 parts of methyl isobutyl ketone to obtain a polymer dilution liquid. Next, 6.5 parts of EMALEX RWIS-305 and the above-mentioned polymer dilution liquid were placed in a 100 mL polycup, and 13.0 parts of the preliminary dispersion of fine particles OC-1 were added while stirring with a disperser, and then stirred and mixed at 2000 rpm for 15 minutes to obtain a defoamer sample C17.

[0346] <Defoamer Sample C19>

[0347] Into a 100 mL polycup, EMALEX RWIS-305: 7.4 parts, Durasyn 164 (polyalphaolefin manufactured by INEOS Oligmers, component B): 27.2 parts, and KF-96-50CS (polydimethylsiloxane manufactured by Shin-Etsu Chemical Co., Ltd., non-component B): 0.7 parts were charged, and while stirring with a disperser, 29.7 parts of the preliminary dispersion of fine particles OC-1 was added, and then stirred and mixed at 2000 rpm for 15 minutes to obtain a defoamer sample C19.

[0348] <Defoamer Sample C20>

[0349] Into a 100 mL polycup were placed 1.2 parts of Sylophobic 100 (hydrophobic silica manufactured by Fuji Silicon Chemical Co., Ltd., non-C component), 5.8 parts of Nipsil SS-30P (hydrophobic silica manufactured by Tosoh Silicon Chemical Co., Ltd., non-C component), and 93.0 parts of COSMO PURE SPIN G (hydrogenated refined paraffin manufactured by COSMO Petroleum Lubricants Co., Ltd.), and the mixture was stirred and mixed at 3500 rpm for 15 minutes to obtain a defoamer sample C20 (silica containing a defoamer). In addition, the methanol wetting value (M value) and the volume average particle size of Sylophobic 100 and Nipsil SS-30P were measured. The M value indicates the degree of hydrophobicity. The higher the M value, the lower the hydrophilicity. It is expressed by the volume ratio of the minimum amount of methanol required to uniformly disperse hydrophobic particles in a mixed solution of water and methanol. Here, the M value is obtained by the following method. Add 0.2g of the test sample (Sylophobic 100 and Nipsil SS-30P) to 50mL of water in a 250mL beaker, and continue to drop methanol until the entire amount of the test sample is suspended in the burette. At this time, the solution in the beaker is constantly stirred with a magnetic stirrer, and the time point when the entire amount of the test sample is uniformly suspended in the solution is taken as the end point, and the volume percentage of methanol in the liquid mixture of the beaker at the end point is taken as the M value. In addition, regarding the volume average particle size, Microtrac MT-3000EXII / USVR is used as a laser diffraction particle size analyzer, 2-propanol is circulated, and the 50% cumulative volume average particle size is measured. The M values ​​and volume average particle sizes of Sylophobic 100 and Nipsil SS-30P measured as described above are as follows.

[0350] Sylophobic 100

[0351] M value: 60; volume average particle size: 2.4 μm

[0352] Nipsil SS-30P

[0353] M value: 60; volume average particle size: 17.5 μm

[0354] <Defoamer Sample C21>

[0355] Into a 100 mL polycup, EMALEX RWIS-305: 3.4 parts, Durasyn 164: 12.5 parts, and while stirring with a disperser, 13.6 parts of the preliminary dispersion of fine particles OC-1 and 9.7 parts of the defoamer sample C20 were added, followed by stirring and mixing at 2000 rpm for 15 minutes to obtain a defoamer sample C21.

[0356] <Defoamer Sample C22>

[0357] Into a 100 mL plastic cup were placed 3.4 parts of EMALEX RWIS-305, 12.5 parts of Durasyn 164, 10.2 parts of Merveille 30, and 2.8 parts of ethanol, and while stirring with a disperser, 9.7 parts of defoamer sample C20 was added, followed by stirring and mixing at 2000 rpm for 15 minutes to obtain defoamer sample C22.

[0358] <Defoamer Sample C23>

[0359] 1.2 parts of Sylophobic 100 (hydrophobic silica manufactured by Fuji Silicon Chemical Co., Ltd., non-C component), 5.8 parts of Nipsil SS-30P (hydrophobic silica manufactured by Tosoh Silicon Chemical Co., Ltd., non-C component), 73.4 parts of Merveille 30 and 19.6 parts of ethanol were added, and the mixture was stirred and mixed at 2000 rpm for 15 minutes using a disperser to prepare a silica slurry. Next, EMALEX RWIS-305: 4.6 parts, Durasyn 164: 16.9 parts, Merveille 30: 13.8 parts, and ethanol: 3.7 parts were placed in a 100 mL polycup, and 13.1 parts of silica slurry was added while stirring with a disperser. The mixture was stirred and mixed at 2000 rpm for 15 minutes to obtain a defoamer sample C23.

[0360] <Defoamer Sample C24>

[0361] After preparing silica slurry in the same manner as defoamer sample C23, EMALEX RWIS-305: 4.6 parts, Durasyn 164: 16.9 parts were placed in a 100 mL polycup, and while stirring with a disperser, 18.5 parts of the preliminary dispersion of fine particles OC-1 and 13.1 parts of silica slurry were added, and then stirred and mixed at 2000 rpm for 15 minutes to obtain defoamer sample C24.

[0362] <Defoamer Sample C25>

[0363] 7.5 parts of EMALEX RWIS-305, 27.5 parts of Durasyn 164, 24.0 parts of Merveille 30, and 6.0 parts of ethanol were placed in a 100 mL polycup, and the mixture was stirred and mixed at 2000 rpm for 15 minutes to obtain a defoamer sample C25.

[0364] The compositions of the defoaming agent samples prepared as described above are shown in Tables 5 to 11 below.

[0365]

Table 5

[0366] Table 5 Composition of defoamer samples (Examples E1-7)

[0367]

[0368]

Table 6

[0369] Table 6 Composition of defoamer samples (Examples E8-18)

[0370]

[0371]

Table 7

[0372] Table 7 Composition of defoamer samples (Examples E19-31)

[0373]

[0374]

[0375]

Table 8

[0376] Table 8 Composition of defoamer samples (Examples E32-44)

[0377]

[0378]

Table 9

[0379] Table 9 Composition of defoamer samples (Examples E45-54)

[0380]

[0381]

Table 10

[0382] Table 10 Composition of defoamer samples (Comparative Examples C1 to 8)

[0383]

[0384]

Table 11

[0385] Table 11 Composition of defoamer samples (Comparative Examples C9-25)

[0386]

[0387] (Preparation of Water-Based Coating Composition and Test Solution)

[0388] Two kinds of water-based paints (Blank) were prepared by the formulations shown in Tables 12 and 13. The water-based paint shown in Table 12 is a homeotropic paint (a paint that dries at room temperature), and the water-based paint shown in Table 13 is a calcining paint (a paint that undergoes a curing reaction by heating).

[0389]

Table 12

[0390] Table 12 Normally dry paint preparation (Blank)

[0391]

[0392]

Table 13

[0393] Table 13 Sintering coating preparation (Blank)

[0394]

[0395] <Preparation of Water-Based Coating Composition for Normally Dry Coating>

[0396] In a 300 mL glass beaker, 100 parts of the normally dry paint in Table 12 were weighed, and 1 part each of the defoamers E1 to E44 and C1 to C24 obtained as described above was added dropwise for 1 minute while stirring at 1000 rpm to obtain the water-based paint compositions of Examples 1 to 44 (Table 14) and Comparative Examples 1 to 24 (Table 15).

[0397] <Preparation of test solution for evaluation test of normally dry paint preparation>

[0398] Use installation The water-based coating compositions of Examples 1 to 44 and Comparative Examples 1 to 24 obtained as described above were dispersed at 2000 rpm using a disperser equipped with a Cowles blade (preliminary high shear process). Regarding the dispersion time, a dispersion liquid dispersed for 5 minutes (hereinafter, sometimes referred to as a "5-minute dispersion") and a dispersion liquid dispersed for 20 minutes (hereinafter, sometimes referred to as a "20-minute dispersion") were prepared for each water-based coating composition. The 5-minute dispersion and the 20-minute dispersion performed in this process correspond to a short high shear process and a long high shear process, respectively. The higher the specific gravity recovery rate of the test liquid dispersed for 20 minutes, the better the shear resistance.

[0399] <Preparation of a water-based coating composition for baking coating preparation: for 5-minute dispersion>

[0400] In a 300 mL glass beaker, 100 parts of the baking coating of Table 13 were weighed, and 1 part each of the defoamers E9, E11 to 13, E15, E18, E24, E27, E32, E33, E45 to E54, and C15, C20, C23, and C25 obtained as described above were added dropwise while stirring at 1000 rpm for 1 minute to obtain water-based coating compositions (for 5-minute dispersions) of Examples 45 to 64 and Comparative Examples 25 to 28 (above, Table 16).

[0401] <Preparation of Test Solution (5-minute Dispersion) for Evaluation Test of Baking Paint Preparation>

[0402] Use installation The water-based coating compositions of Examples 45 to 64 and Comparative Examples 25 to 28 obtained as described above were dispersed in a disperser having a Cowles blade at 2000 rpm for 5 minutes (preliminary high shearing step). The 5-minute dispersion in this step corresponds to a short-time high shearing step.

[0403] <Preparation of a water-based coating composition for baking coating preparation: for 20-minute dispersion>

[0404] In a 300 mL glass beaker, 100 parts of the baking coating of Table 13 were weighed, and 1 part each of the defoamers E9, E11 to 13, E15, E18, E24, E27, E32, E33, E45 to E54, and C15, C20, C23, and C25 obtained as described above were added dropwise while stirring at 1000 rpm for 1 minute to obtain water-based coating compositions (for 20-minute dispersions) of Examples 45 to 64 and Comparative Examples 25 to 28 (above, Table 16).

[0405] <Preparation of Test Solution (20-minute Dispersion) for Evaluation Test of Baking Paint Preparation>

[0406] Use installation The water-based coating compositions of Examples 45 to 64 and Comparative Examples 25 to 28 obtained as described above were dispersed for 20 minutes using a Cowles blade disperser at 2000 rpm (preliminary high shear process). The 20-minute dispersion performed in this process is equivalent to a long high shear process. The higher the specific gravity recovery rate of the test liquid dispersed for 20 minutes, the better the shear resistance.

[0407] The dispersions (5-minute dispersions and 20-minute dispersions) of Examples 1 to 64 and Comparative Examples 1 to 28 obtained in the above preliminary high shearing step were transferred to a 200 mL polycup, degassed for 2 minutes in the degassing mode using THINKY MIXER ARE-310 (manufactured by THINKY Co., Ltd.), and allowed to stand at room temperature for more than 2 hours before use as test solutions for Examples and Comparative Examples (degassing step).

[0408] [Evaluation method]

[0409] The water-based coating compositions of Examples 1 to 64 and Comparative Examples 1 to 28 obtained as described above were subjected to evaluation tests as follows.

[0410] (Evaluation of shear resistance)

[0411] 100 portions of the test solution obtained in the degassing step were transferred to a 200 mL polycup and dispersed at 2000 rpm for 5 minutes using a disperser equipped with a Clover blade to perform foaming (foaming step). The dispersion in this step refers to the foaming step. In addition, the high shear step and the foaming step were separated in order to make the conditions in the foaming step the same.

[0412] <Evaluation of the preparation of dry paint>

[0413] The specific gravity of the test liquid was measured using a specific gravity cup 1 minute and 5 minutes after foaming, and the percentage relative to the specific gravity of the test liquid before foaming was calculated as the specific gravity recovery rate. The closer the specific gravity recovery rate is to 100%, the better the defoaming property. The time of 1 minute and 5 minutes when calculating the specific gravity recovery rate are both the time required for specific gravity recovery. The specific gravity recovery rate after 1 minute was mainly evaluated as an indicator related to foam suppression, and the specific gravity recovery rate after 5 minutes was mainly evaluated as an indicator related to bubble breaking.

[0414] Specific gravity recovery rate (after 1 minute) = (specific gravity 1 minute after the test liquid foams) / (specific gravity before the test liquid foams) × 100 [%]

[0415] Specific gravity recovery rate (after 5 minutes) = (specific gravity 5 minutes after the test liquid foams) / (specific gravity before the test liquid foams) × 100 [%]

[0416] The shear resistance was evaluated according to the following criteria. In addition, when the specific gravity recovery rate (1 minute) and the specific gravity recovery rate (5 minutes) in the test liquid dispersed for 5 minutes were both C rating or above, and at least one of the specific gravity recovery rate (1 minute) and the specific gravity recovery rate (5 minutes) in the test liquid dispersed for 20 minutes was C rating or above, it was judged that the shear resistance required by the present invention was possessed.

[0417] <Evaluation Criteria for Specific Gravity Recovery Rate (1 Minute)>

[0418] Specific gravity recovery rate (1 minute) [%] 95% or more: Very good (A)

[0419] Specific gravity recovery rate (1 minute) [%] 85% or more and less than 95%: Excellent (B)

[0420] Specific gravity recovery rate (1 minute) [%] is 75% or more and less than 85%: The effect is acceptable (C)

[0421] Specific gravity recovery rate (1 minute) [%] less than 75%: poor defoaming effect (D)

[0422] <Evaluation Criteria for Specific Gravity Recovery Rate (5 Minutes)>

[0423] Specific gravity recovery rate (5 minutes) [%] 98% or more: Very good (A)

[0424] Specific gravity recovery rate (5 minutes) [%] 90% or more and less than 98%: Excellent (B)

[0425] Specific gravity recovery rate (5 minutes) [%] is 80% or more and less than 90%: The effect is acceptable (C)

[0426] Specific gravity recovery rate (5 minutes) [%] less than 80%: poor defoaming effect (D)

[0427] <Evaluation of Sintering Paint Preparation>

[0428] The specific gravity of the test liquid was measured using a specific gravity cup 1 minute and 5 minutes after foaming, and the percentage relative to the specific gravity of the test liquid before foaming was calculated as the specific gravity recovery rate. The closer the specific gravity recovery rate is to 100%, the better the defoaming property. The time of 1 minute and 5 minutes when calculating the specific gravity recovery rate is the time required for the specific gravity to recover. The specific gravity recovery rate after 1 minute was mainly evaluated as an indicator related to the foam suppression property, and the specific gravity recovery rate after 5 minutes was mainly evaluated as an indicator related to the bubble breaking property.

[0429] Specific gravity recovery rate (after 1 minute) = (specific gravity 1 minute after the test liquid foams) / (specific gravity before the test liquid foams) × 100 [%]

[0430] Specific gravity recovery rate (after 5 minutes) = (specific gravity 5 minutes after the test liquid foams) / (specific gravity before the test liquid foams) × 100 [%]

[0431] The shear resistance was evaluated according to the following criteria. In addition, when the specific gravity recovery rate (1 minute) and the specific gravity recovery rate (5 minutes) in the test liquid dispersed for 5 minutes were both C rating or above, and at least one of the specific gravity recovery rate (1 minute) and the specific gravity recovery rate (5 minutes) in the test liquid dispersed for 20 minutes was C rating or above, it was judged that the shear resistance required by the present invention was possessed.

[0432] <Evaluation Criteria for Specific Gravity Recovery Rate (1 Minute)>

[0433] Specific gravity recovery rate (1 minute) [%] 99.5% or more: Very good (A)

[0434] Specific gravity recovery rate (1 minute) [%] 95% or more, less than 99.5%: Excellent (B)

[0435] Specific gravity recovery rate (1 minute) [%] is 90% or more and less than 95%: The effect is acceptable (C)

[0436] Specific gravity recovery rate (1 minute) [%] less than 90%: poor defoaming effect (D)

[0437] <Evaluation Criteria for Specific Gravity Recovery Rate (5 Minutes)>

[0438] Specific gravity recovery rate (5 minutes) [%] 99.5% or more: Very good (A)

[0439] Specific gravity recovery rate (5 minutes) [%] 95% or more and less than 99.5%: Excellent (B)

[0440] Specific gravity recovery rate (5 minutes) [%] is 90% or more and less than 95%: The effect is acceptable (C)

[0441] Specific gravity recovery rate (5 minutes) [%] less than 90%: poor defoaming effect (D)

[0442] In addition, since the foaming property and specific gravity of the paint (Blank) without adding a defoamer vary depending on the paint formulation, the evaluation criteria for the shear resistance of the baked paint formulation using ACD-2001 are different from the evaluation criteria for the shear resistance of the normally dry paint formulation using AP-3900.

[0443] (Evaluation of coating appearance)

[0444] The test solutions prepared as a normal-drying paint and the test solutions prepared as a baked paint were applied to a glass plate and the appearance of the coating films dried and baked was evaluated.

[0445] <Evaluation of the preparation of dry paint>

[0446] The test solution obtained in the degassing step was applied to a glass plate using a bar coater #42, and dried at room temperature for one day, and the appearance of the coating film was evaluated. The coating appearance was evaluated based on the following criteria.

[0447] ○ (excellent): No fish-eye shrinkage was observed on the coating film

[0448] ○1 (Good): No more than 3 shrinkage holes are identified on the coating film

[0449] △ (OK): No more than 3 fish-eye-shaped shrinkages can be seen on the coating film

[0450] × (poor): More than three fish-eye-shaped shrinkages or significant roughening were observed on the coating film.

[0451] <Evaluation of Sintering Paint Preparation>

[0452] The test solution obtained in the degassing step was applied to a glass plate using a 200 μm applicator, and a film was formed under the conditions of setting at room temperature for 5 minutes, preheating at 80°C for 5 minutes, and calcining at 140°C for 30 minutes, and the appearance of the coating film was evaluated. The coating appearance was evaluated according to the following criteria.

[0453] ○ (excellent): No fish-eye shrinkage was observed on the coating film

[0454] ○-(Good): Three or fewer shrinkage cavities were identified in the coating film.

[0455] △ (OK): No more than 3 fish-eye-shaped shrinkages can be seen on the coating film

[0456] × (poor): More than three fish-eye-shaped shrinkages or significant roughening were observed on the coating film.

[0457] (Evaluation of surface coating properties)

[0458] The presence or absence of the risk of topcoat obstruction is determined by whether the water-based coating composition contains a silicone compound ("presence or absence of silicone:").

[0459] No risk of topcoat obstruction due to silicone: No (does not contain silicone compounds)

[0460] Risk of topcoat obstruction due to silicone: Yes (contains silicone compounds)

[0461] [Evaluation results]

[0462] The results of the performance evaluation as described above are shown in Tables 14 to 16. In addition, for Blank (a sample without defoaming agent added), the data of specific gravity recovery rate (1 minute) and specific gravity recovery rate (5 minutes) recorded in the "5-minute dispersion" column of Tables 15 and 16 are the results of foaming a sample that was not subjected to a preliminary high shearing process in the foaming process and confirming the specific gravity. In addition, for the Blank sample, the preliminary high shearing process was performed for 20 minutes. As a result, the foaming in the preliminary high shearing process was significant, so the shear resistance evaluation test was discontinued.

[0463]

Table 14

[0464] Table 14 Evaluation results of the normal dry paint preparation (Examples 1 to 44)

[0465]

[0466]

[0467]

Table 15

[0468] Table 15 Evaluation results of normally dry paint preparation (Comparative Examples 1 to 24, Blank)

[0469]

[0470] *Results evaluated without prior high shearing process

[0471]

Table 16

[0472] Table 16 Evaluation results of baking paint preparation (Examples 45 to 64, Comparative Examples 25 to 28, Blank)

[0473]

[0474] *Results evaluated without prior high shearing process

[0475] The water-based coating compositions of Examples 1 to 64 all had the performance required by the present invention in terms of shear resistance, coating appearance, and topcoatability.

[0476] Comparison of Examples 1, 9, 12, and 16 shows that when the HLB of the nonionic surfactant (A) is 2 or more, the coating appearance tends to be particularly excellent.

[0477] Comparison of Examples 1, 20, and 23 shows that when the SP value of the polymer (B) is 9.5 or less, the shear resistance is particularly excellent.

[0478] Comparison of Examples 1, 21, 27 and 31 shows that when the weight average molecular weight of the polymer (B) is 300,000 or less, shear resistance and coating appearance are particularly excellent.

[0479] Comparison of Examples 1, 34, 36, and 38 shows that when the aspect ratio of the organic solid fine particles (C) is in the range of 2.0 to 11, the shear resistance is particularly excellent.

[0480] On the other hand, as a defoamer component, Comparative Examples 1 to 3 and 25 that do not contain organic solid particles (C) and Comparative Examples 4 to 6 that do not contain nonionic surfactants (A) and polymers (B) all have poor shear resistance. In addition, in the water-based coating composition of Comparative Example 3, separation of the defoamer occurred. In addition, Comparative Example 25 is an example in which the organic solid particles (C) are replaced with Merveille 30.

[0481] In addition, Comparative Examples 7, 17, and 19 containing silicone compounds as defoaming agent components and Comparative Examples 8, 20 to 24 containing hydrophobic silica had poor coating appearance. Furthermore, in Comparative Examples 7, 17, and 19 containing silicone compounds, there was a risk of top coating failure due to the presence of silicone compounds.

[0482] In addition, in Comparative Examples 9 to 14 containing a surfactant (non-component A) having an HLB of more than 16 as a nonionic surfactant, the defoamer composition (defoamer sample) was separated, and therefore subsequent tests were discontinued.

[0483] In addition, Comparative Examples 15 to 19 containing a polymer (non-B component) not corresponding to the polymer (B) of the present invention as a polymer were inferior in at least one of shear resistance or coating appearance. In particular, Comparative Examples 17 and 19 containing a silicone compound as a polymer were excellent in shear resistance but inferior in coating appearance.

[0484] In addition, Comparative Examples 20 to 24 containing inorganic solid fine particles (non-component C) as solid fine particles were excellent in shear resistance but had poor coating appearance.

Claims

1. A defoamer composition, a defoamer composition for water-based coatings, characterized in that: contain: A nonionic surfactant (A) having at least one hydrophilic portion selected from the group consisting of an ethylene glycol portion, a polyethylene glycol portion and a polyol portion in the molecule, and having an HLB of 1 to 16; The polymer (B) does not have the hydrophilic part in the molecule, has an SP value of 7.5 to 12, and has a weight average molecular weight of 400 to 1,000,000; and The organic solid fine particles (C) are in a solid state in the defoamer composition at 25°C.

2. The defoamer composition according to claim 1, characterized in that The nonionic surfactant (A) is one or more selected from the group consisting of ethylene glycol fatty ethers, polyoxyalkylene fatty ethers, polyoxyalkylene aromatic ethers, polyoxyalkylene fatty acid esters, oxyalkylene addition derivatives of castor oil, oxyalkylene addition derivatives of hydrogenated castor oil, polyoxyalkylene polyol ethers, polyol fatty acid esters, oxyalkylene addition derivatives of polyol fatty acid esters, polyoxyalkylene alkylamides, acetylene glycols and their derivatives, oxyalkylene addition derivatives of acetylene glycols, polyoxyethylene-polyoxypropylene block copolymers, and polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers.

3. The defoamer composition according to claim 1, characterized in that The polymer (B) is one or more polymers selected from the group consisting of polyvinyl alkyl ether, polybutadiene, polybutene, polyisoprene, poly-alpha-olefin, polyalkyl (meth) acrylate, copolymer of dibasic acid ester, polyvinyl fatty acid ester, copolymer of alkyl (meth) acrylate and vinyl fatty acid ester, and polyalkylene glycol derivatives, wherein the polyalkylene glycol derivative does not have the ethylene glycol portion, the polyethylene glycol portion and the polyol portion, and the weight average molecular weight of the polyalkylene glycol derivative is 400 to 1,000,000.

4. The defoamer composition according to claim 1, characterized in that The organic solid particles (C) are one or more solid particles selected from the group consisting of amide, urea, polyethylene, oxidized polyethylene, acid-modified polyethylene, and hydrogenated castor oil.

5. The defoamer composition according to claim 4, characterized in that The amide is a fatty acid diamide obtained by reacting a fatty acid selected from the group consisting of an alkyl fatty acid and a hydroxy fatty acid and containing at least one hydroxy fatty acid, with a diamine containing one or more diamines selected from the group consisting of an alkylenediamine having 2 to 6 carbon atoms and meta-xylylenediamine.

6. The defoamer composition according to claim 1, characterized in that The aspect ratio of the crystals of the organic solid particles (C) is 1.1-100.

7. The defoamer composition according to claim 1, characterized in that further comprising an organic medium (D) other than water which does not have the hydrophilic part in the molecule and is liquid at 25°C, The weight average molecular weight of the organic medium (D) is less than 400.

8. The defoamer composition according to claim 7, characterized in that The organic medium (D) is one or more selected from the group consisting of hydrocarbon oils, alcohols, glycol ethers, and glycol esters.

9. The defoamer composition according to claim 1, characterized in that Does not contain silicone compounds.

10. A water-based coating composition, characterized in that: The defoamer composition according to any one of claims 1 to 9 and an aqueous resin are contained. 11 . An article coated with a coating agent comprising the defoaming agent composition according to claim 1 .

Citation Information

Patent Citations

  • Composition for defoaming and its production

    JP1989006803B2

  • Antifoaming agent composition

    JP2001212403A

  • Preparation for general defoaming agent and its application

    CN101053706A

  • Defoamer

    CN102300612A

  • Antifoaming agent

    JP2013141664A